Spatial models cannot compensate for sampling designs unstructured relative to isotopic variation: implications for baseline isoscape development in the Mediterranean Sea - Sarah Magozzi; Clive N. Trueman; Matthew R.D. Cobain; Kirsteen M. MacKenzie; Katie St. John Glew; José A. Canseco; Eric Díaz-Delgado; Emanuela Fanelli; Paola Rumolo; Joan E. Cartes; Boris Espinasse; Davide Agnetta; et al. (Progress in Oceanography, 2026)

Integrated histone and proteome analyses reveal convergent and distinct hepatotoxic mechanisms of tenuazonic acid and deoxynivalenol - Yasmine Bader; Ruben Almey; Thijs Lefever; Amélie De Maesschalck; Thanos Mouchtaris-Michailidis; Tess Goessens; Sarah De Saeger; Tine Claeys; Simon Daled; Marthe De Boevre; Maarten Dhaenens (Journal of Hazardous Materials, 2026)

Anti-environmental political agendas, firearm deregulation and illegal hunting in Brazil - Hani R. El Bizri; Thais Queiroz Morcatty; Marcela A. Oliveira; Aline Pessutti Rampini; Simon Knoop; Julia E. Fa; Kacie Henson; Camila Alvez Islas; Gabriel Favero Massocato; Arnaud L.J. Desbiez; João Vitor Campos-Silva; Daniel Zani La Laina; et al. (Biological Conservation, 2026)

Use of a novel integrated dilator-needle system for transseptal puncture in three dogs undergoing left atrial decompression. - Fabio Sarcinella; Sophie Goodrich; Katie Glyde; Sarah Smith; Ruth Willis; Simon Swift; Siddharth Sudunagunta (Journal of Veterinary Cardiology, 2026)

Using life-history information to identify management priorities within an emergent multi-species grey mullet fishery - Calum J. Pritchard; Ayşegül Tuğçe Han; Andrew Macleod; Rachel M. Turnbull; Jamie Small; Sarah Birchenough; Simon Pengelly; Benjamin J. Ciotti (Fisheries Research, 2026)

Lived experiences of food-related emotional expectancies across socioeconomic groups in adults with overweight/obesity: A co-produced mixed-methods study - Maddy Roberts; Isabelle Ince; Beccie Neubeck; Sarah-Kate O'Hara; Tracy Hammond; Simon Collyer; Helen West; Anna Chisholm; Eric Robinson; Jenna R. Cummings (Appetite, 2026)

Environmental uncertainty affects movement and space-use in sheep - Sarah T. Bartsch; William H. E. J. van Wettere; Simon C. Griffith; Stephan T. Leu (Behavioral Ecology and Sociobiology, 2026)
Animals regularly experience periods of food uncertainty due to seasonal changes and environmental variability. Further, the changing climate is leading to more variable weather patterns, which alter environmental conditions, and can result in resource distributions being less predictable in space and time. How animals respond to uncertain conditions, and in particular a changing distribution of food resources, remains largely unclear and is an important question in the field of movement and animal ecology. We used an experimental approach to study how Merino sheep ( Ovis aries ) respond to different levels of food location uncertainty in a drought-impacted region of the Australian arid zone. Sheep were unfamiliar with the experimental food locations at the start and progressively decreased their uncertainty (i.e., increased their environmental knowledge) when discovering an increasing number of foraging patches. We tracked 50 sheep with GPS collars (1 location every 15 s) and deduced their movement and space use behaviour. When food uncertainty decreased, individuals moved more directionally (greater step length, smaller turn angles) and moved greater distances per day. They also had larger daily ranges. Displacement (distance between first and last location of the day) increased once and otherwise remained similar across levels of uncertainty. Our study demonstrates how an arid zone ungulate, in a large 600 ha enclosed paddock, adjusted its movement and space use behaviour as it gained environmental information on food distribution. Our study provides important insights into how animals cope with variable environments in order to forage efficiently during periods of uncertainty. Significance statement Food distributions are often unpredictable over time, with climate change exacerbating variability. Understanding how animals respond to periods of environmental uncertainty is crucial to predict animal movement in space and time. We used an experimental approach and investigated how different levels of food location uncertainty affected the movement and space-use behaviour in sheep freely moving in a large 600 ha paddock. We used the number of discovered experimental food patches as a proxy for environmental knowledge (inverse of uncertainty). Movement was faster and more directional, and daily range size increased as food uncertainty decreased and sheep gained knowledge about the food locations. Our study demonstrates how an arid zone ungulate adjusted its movement and space use behaviour as it gained environmental information about food patch distributions.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

In situ Rb–Sr geochronology records multiple fluid pulses in Neoproterozoic sequences from the Lubambe-Mingomba Cu deposits in the Zambian Copperbelt - Victor Ikechukwu Vincent; Koen Torremans; Darwinaji Subarkah; Sarah E. Gilbert; Juraj Farkaš; Alan S. Collins; Jon Stacey; Aileen L. Doran; Simon Jones; Murray W. Hitzman (Precambrian Research, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Insights into the impact of climate change on economic trajectories of North Sea demersal fisheries derived from a spatially explicit bio-economic model - Erik Sulanke; Øystein Hermansen; Matt Elliott; Arina Motova; Marta Moran-Quintana; Sarah Simons (Ocean & Coastal Management, 2026)

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Developing and ranking a national red list of Saudi Arabian plants through meta-analysis - Christopher Clarke; Zahra Alhawsa; Simon John Attwood; Sarah Alsaidalani; Mark Tester (Biological Conservation, 2026)

Mapping the Journey and Experience of People Living With Post-Stroke Spasticity - Arlene Wilkie; Diana Wong Ramos; Grethe Lunde; Maja Bozinovska Smiceska; Marina Charalambous; Elen Kirt; Georgi Georgiev; Jelka Jansa; Liliia Zviagina; Simon Page; Sarah Thomas; Oleks Gorbenko (Toxicon, 2026)

Effect of Early Use of Botulinum Toxin A on Goal Attainment in Post-Stroke Spasticity - Atul Patel; Jinming Zhang; Simon Page; Sarah Harding; Mathieu Beneteau; Alberto Esquenazi (Toxicon, 2026)

Sleep disturbances and Alzheimer’s disease: a multiscale approach from exposome to neurobiology and precision medicine - Masoud Tahmasian; Jorik D. Elberse; Reihaneh Ahmadi; Wen Liu; Ivana Rosenzweig; Sarah Genon; Simon B. Eickhoff; Bryce A. Mander (GeroScience, 2026)
Sleep disturbances and Alzheimer’s disease (AD) are interconnected public health challenges. However, the underlying mechanisms of their complex relationships remain elusive. Here, we propose a hypothetical integrative, stream-like model outlining how external and internal exposome factors accelerate brain aging, thereby exacerbating circadian dysregulation, orexin-mediated hyperexcitability, metabolic imbalance, and inflammaging. These changes can lead to increased sleep fragmentation and reduced slow-wave sleep, triggering widespread neuroinflammation, glymphatic dysfunction, and the accumulation and dissemination of beta-amyloid and tau peptides. These processes collectively accelerate synaptic dysfunction, neuronal loss, and cognitive decline. We also highlight recent neuroimaging evidence that elucidates the neural substrates underlying the relationship between poor sleep and AD. Moreover, tackling their shared burden necessitates the active consideration of inter-individual variability in vulnerable populations through artificial intelligence and computational approaches, aligning with the core tenets of precision medicine. We hope this review encourages clinicians to prioritize monitoring and treating sleep disturbances to reduce the incidence, severity, and consequences of dementia in the general population.

Bayesian assessment of three serological tests for the screening of Trypanosoma cruzi in hunting dogs of Virginia and West Virginia, USA - Juan Pablo Guarda; Aida Estefania Pereyra-Cruzado; Walter Logan; Trinity Gleich; Sarah A. Hamer; Simon M. Firestone; Roger Ramirez-Barrios; Cristobal Verdugo (Preventive Veterinary Medicine, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Seamounts of Cabo Verde: A review of their ecological and economic significance, anthropogenic impacts, and conservation needs - Covadonga Orejas; Beatriz Vinha; Gillian B. Ainsworth; Sarah Saldanha; Teresa Militão; Christian Mohn; Thor H. Hansteen; Sara S. Ratão; Henk-Jan Hoving; Teresa Amaro; Dominique M.J. Anderson; Deusa Araújo; et al. (Progress in Oceanography, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Thermal infrared characterization of spatially unresolved resident space objects: Prospects from analytical two-component modeling - Stephen Catsamas; Sarah Caddy; Michele Trenti; Benjamin Metha; Simon Barraclough; Robert Mearns; Airlie Chapman; Rachel Webster (Advances in Space Research, 2026)

Life cycle assessment comparing electric and petrol-powered rigid inflatable boats for recreational and harbour-master applications - Amir Bordbar; Badr Moutik; Adam Kyte; Simon Ussher; Keri Collins; Marcin Roszkowski; Tony Wilson; Sarah Fear (Ocean Engineering, 2025)

The Zoo Sphere of Influence Model - Sarah L. Spooner; Susan L. Walker; Simon Dowell; Mara Cristina Marques; Marina Somenzari; Fabiana Lopes Rocha; Eugenia Cordero-Schmidt; Charlotte Hughes; Christine Lee; Charlotte Smith; Jennifer Kelly; Linda Salim; et al. (Biological Conservation, 2025)

Prognostic immunotherapy score (PIS) in patients with advanced urothelial carcinoma treated with pembrolizumab: real-world data and validation from ARON-2 dataset - Alessandro Rizzo; Anas Zayed; Elsa Vitale; Sebastiano Buti; Hideki Takeshita; Simon Crabb; Giandomenico Roviello; Emmanuel Seront; Jose Carlos Tapia; Sarah Scagliarini; Lazar Popovic; Ray Manneh Kopp; et al. (Clinical & Experimental Metastasis, 2025)

Understanding and Predicting Population Response to Anthropogenic Disturbance: Current Approaches and Novel Opportunities - Cassie N. Speakman; Sarah Bull; Sarah Cubaynes; Katrina J. Davis; Sébastien Devillard; John M. Fryxell; Cara A. Gallagher; Elizabeth A. McHuron; Kévan Rastello; Isabel M. Smallegange; Roberto Salguero‐Gómez; Elsa Bonnaud; et al. (Ecology Letters, 2025)
Effective conservation of biodiversity depends on the successful management of wildlife populations and their habitats. Successful management, in turn, depends on our ability to understand and accurately forecast how populations and communities respond to human‐induced changes in their environments. However, quantifying how these stressors impact population dynamics remains challenging. Another significant hurdle at this interface is determining which quantitative approach(es) are most appropriate given data types, constraints and the intended purpose. Here, we provide a cross‐taxa overview of key methodological approaches (e.g., matrix population models) and model elements (e.g., energetics) that are currently used to model the effects of anthropogenic disturbance on wildlife populations. Specifically, we discuss how these modelling approaches differ in their key assumptions, in their structure and complexity, in the questions they are best poised to address and in their data requirements. Our intention is to help overcome some of the methodological biases that might persist across taxonomic specialisations, identify new opportunities to address existing modelling challenges and improve scientific understanding of the direct and indirect impacts of anthropogenic disturbance. We guide users through the identification of appropriate model configurations for different management purposes, while also suggesting key priorities for model development and integration.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Habitability for a connected, unequal and changing world - Harald Sterly; Marion Borderon; Patrick Sakdapolrak; Neil Adger; Ayansina Ayanlade; Alassane Bah; Julia Blocher; Suzy Blondin; Sidy Boly; Timothée Brochier; Loïc Brüning; Simon Bunchuay-Peth; et al. (Global Environmental Change, 2025)

CLAMity: Mixtures of agricultural pesticides as multiple stressors in a bivalve species - Alice Graihagh Guille; Sarah Purnell; Simon Lohery; Corina Ciocan (Journal of Hazardous Materials, 2025)

EuPPollNet : A European Database of Plant‐Pollinator Networks - Jose B. Lanuza; Tiffany M. Knight; Nerea Montes‐Perez; Will Glenny; Paola Acuña; Matthias Albrecht; Maddi Artamendi; Isabelle Badenhausser; Joanne M. Bennett; Paolo Biella; Ricardo Bommarco; Andree Cappellari; et al. (Global Ecology and Biogeography, 2025)
Motivation Pollinators play a crucial role in maintaining Earth's terrestrial biodiversity. However, rapid human‐induced environmental changes are compromising the long‐term persistence of plant‐pollinator interactions. Unfortunately, we lack robust, generalisable data capturing how plant‐pollinator communities are structured across space and time. Here, we present the EuPPollNet (European Plant‐Pollinator Networks) database, a fully open European‐level database containing harmonised taxonomic data on plant‐pollinator interactions referenced in both space and time, along with other ecological variables of interest. In addition, we evaluate the taxonomic and sampling coverage of EuPPollNet, and summarise key structural properties in plant‐pollinator networks. We believe EuPPollNet will stimulate research to address data gaps in plant‐pollinator interactions and guide future efforts in conservation planning. Main Types of Variables Included EuPPollNet contains 1,162,109 interactions between plants and pollinators from 1864 distinct networks, which belong to 52 different studies distributed across 23 European countries. Information about sampling methodology, habitat type, biogeographic region and additional taxonomic rank information (i.e. order, family, genus and species) is also provided. Spatial Location and Grain The database contains 1214 different sampling locations from 13 different natural and anthropogenic habitats that fall in 7 different biogeographic regions. All records are geo‐referenced and presented in the World Geodetic System 1984 (WGS84). Time Period and Grain Species interaction data was collected between 2004 and 2021. Major Taxa and Level of Measurement The database contains interaction data at the species level for 94% of the records, including a total of 1411 plant and 2223 pollinator species. The database includes data on 6% of the European species of flowering plants, 34% of bees, 26% of butterflies and 33% of syrphid species at the European level. Software Format The database was built with R and is stored in ‘.rds’ and ‘.csv’ formats. Its construction is fully reproducible and can be accessed at: https://doi.org/10.5281/zenodo.14747448 .

The Breeding Bird Survey of the United Kingdom - Dario Massimino; Stephen R. Baillie; Dawn E. Balmer; Richard I. Bashford; Richard D. Gregory; Sarah J. Harris; James J. N. Heywood; Leah A. Kelly; David G. Noble; James W. Pearce‐Higgins; Michael J. Raven; Kate Risely; et al. (Global Ecology and Biogeography, 2025)
Motivation Information on species' population trends is essential to assess species' conservation status, make informed environmental decisions and ultimately reduce biodiversity loss. Robust population trends require a long‐term monitoring programme, often using citizen scientists, that ideally generates representative and unbiased data from the study area. Here we present the dataset of the Breeding Bird Survey, the main scheme for monitoring the population changes of common and widespread breeding birds in the United Kingdom, which achieves this through a randomised sampling scheme and defined field methodology. We also describe the modelling approach used to calculate the population trends, which are the main output of the survey. Main Types of Variable Contained The main published dataset contains 7,070,577 records detailing counts of 217 bird species in 7010 grid cells over 30 years. Data for 78 species that are currently regarded as too sensitive to be released at fine resolution are omitted. As an illustration of the main use of this dataset, we provide population change estimates for 119 bird species. Spatial Location and Grain Grid squares (1 × 1 km) are randomly selected using a stratified sampling scheme throughout the United Kingdom, Isle of Man and Channel Islands. Data in a grid square are collected along two 1‐km‐long transects which are subdivided into 200‐m‐long sections. Time Period and Grain Data have been collected every year since 1994, with two major disruptions in 2001 and 2020, when people's movements were nationally restricted. Grid squares are surveyed twice a year during the main breeding season (April to June). Here we present the data collected from 1994 to 2023. Major Taxa Studied and Level of Measurement Bird species. Software Format Data are supplied as comma‐separated text files.

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Shaping multilateral regional governance of climate and forests: Exploring the influence of Forest industry lobbying on state participation - Fredy David Polo-Villanueva; Simon Schaub; Laura Rivadeneira; Jale Tosun; Lukas Giessen; Sarah Lilian Burns (Forest Policy and Economics, 2024)

Tracking the first electron transfer step at the donor side of oxygen-evolving photosystem II by time-resolved infrared spectroscopy - Mohamad Yahia Dekmak; Sarah M. Mäusle; Janosch Brandhorst; Philipp S. Simon; Holger Dau (Photosynthesis Research, 2024)
In oxygen-evolving photosystem II (PSII), the multi-phasic electron transfer from a redox-active tyrosine residue (TyrZ) to a chlorophyll cation radical (P680 + ) precedes the water-oxidation chemistry of the S-state cycle of the Mn 4 Ca cluster. Here we investigate these early events, observable within about 10 ns to 10 ms after laser-flash excitation, by time-resolved single-frequency infrared (IR) spectroscopy in the spectral range of 1310–1890 cm −1 for oxygen-evolving PSII membrane particles from spinach. Comparing the IR difference spectra at 80 ns, 500 ns, and 10 µs allowed for the identification of quinone, P680 and TyrZ contributions. A broad electronic absorption band assignable P680 + was used to trace largely specifically the P680 + reduction kinetics. The experimental time resolution was taken into account in least-square fits of P680 + transients with a sum of four exponentials, revealing two nanosecond phases (30–46 ns and 690–1110 ns) and two microsecond phases (4.5–8.3 µs and 42 µs), which mostly exhibit a clear S-state dependence, in agreement with results obtained by other methods. Our investigation paves the road for further insight in the early events associated with TyrZ oxidation and their role in the preparing the PSII donor side for the subsequent water oxidation chemistry.

Characterization and screening of new Metarhizium isolates to control the coconut rhinoceros beetle in the Pacific islands - Laura F. Villamizar; Gloria P. Barrera; Alphonse Luange; Katayo Sagata; Paul Gende; Simon Chris; Helen Tsatsia; Freda Mudu; Mitchell Weston; Chikako van Koten; Sarah Mansfield; Trevor A. Jackson; et al. (Fungal Biology, 2024)

Correction: Prey targeted by lactating Weddell seals (Leptonychotes weddellii) in Erebus Bay, Antarctica - Rose T. N. Foster-Dyer; Kimberly T. Goetz; Takashi Iwata; Rachel R. Holser; Sarah A. Michael; Craig Pritchard; Simon Childerhouse; Daniel P. Costa; David G. Ainley; Matthew H. Pinkerton; Michelle A. LaRue (Polar Biology, 2024)

Prey targeted by lactating Weddell seals (Leptonychotes weddellii) in Erebus Bay, Antarctica - Rose T. N. Foster-Dyer; Kimberly T. Goetz; Takashi Iwata; Rachel R. Holser; Sarah A. Michael; Craig Pritchard; Simon Childerhouse; Daniel P. Costa; David G. Ainley; Matthew H. Pinkerton; Michelle A. LaRue (Polar Biology, 2024)
Female Weddell seals ( Leptonychotes weddellii ) display a mixed capital-income breeding strategy, losing up to 40% of their body mass between birthing and weaning their pups. How and when they regain energy stores, however, remains to be fully explored. To better understand the foraging by lactating Weddell seals, we fitted time-depth recorders and head-mounted cameras on 26 seals in Erebus Bay, Ross Sea, for ~ 5 days in November and December 2018 and 2019. We aimed to (1) identify prey species and foraging depth and (2) investigate relationships between seal physiology and demographics and probability of foraging. We recorded 2782 dives, 903 of which were > 50 m, maximum depth was 449.3 m and maximum duration was 31.1 min. Pup age likely contributes to the probability of a lactating Weddell seal foraging (Est. = 1.21 (SD = 0.61), z = 1.97, p = 0.0484). Among 846 prey encounters, the most frequent prey items were crustaceans (46.2%) and Antarctic silverfish ( Pleuragramma antarcticum , 19.0%); two encounters were observed with juvenile Antarctic toothfish ( Dissostichus mawsoni , 0.2%). We identified substantial variability in foraging behaviour, individually and between locations, and found that lactating seals target many species and some may specialise on certain prey groups.

Examining Bald Eagle Contaminant Exposure and Reproductive Risk Above and Below Dams on Great Lakes Tributaries - Carly Jasmine Eakin; Lisa Williams; Jeremy Moore; Mandy Annis; David Best; Sarah Warner; William Bowerman; Latice Fuentes; Kendall Simon; Brandon Armstrong (Archives of Environmental Contamination and Toxicology, 2024)
Removing lowermost dams can reestablish fish passage on Great Lakes tributaries. This can increase the transfer of contaminants from anadromous fish to piscivorous wildlife upstream; however, concentrations of bioaccumulative contaminants in Great Lakes fish have decreased over the last several decades. We analyzed concentrations of PCBs and the toxic equivalence (TEQs) calculated from PCBs, DDTs, other organochlorine pesticides, and PBDEs in the plasma of bald eagle nestlings above and below lowermost dams on five river systems in Michigan from 1999 to 2013. We examined relationships between contaminants and metrics of reproductive success from 1997 to 2018, including the effects of year and location relative to the lowermost dam. Σ 20 PCB and p,p’ -DDE were important in characterizing differences in contaminant mixtures above and below dams. Concentrations of contaminants were generally greater below dams than above. There were generally greater nest success and more nestlings per nest below dams, but nest location explained little variability ( R 2 values = 0.03–0.15). Neither Σ 20 PCB nor p,p’ -DDE was a significant predictor of 5-year productivity means by river reach despite concentrations exceeding previously established effects thresholds for healthy bald eagle populations in the Great Lakes (≥ 1 nestling/nest). Our study indicates that dams may continue to reduce the upstream movement of contaminants to bald eagles, but at the measured concentrations, contaminants did not impair productivity and reproductive success as indicated by nestlings per nest. Additional information about population dynamics could clarify population-level effects of contaminants on bald eagles and to what degree these populations are self-sustaining throughout the Great Lakes.

Metabarcoding and morphological analysis of diets of mesopelagic fishes in the NW Atlantic Slope Water - Ann Bucklin; Paola G. Batta-Lona; Jennifer M. Questel; Helena McMonagle; Melissa Wojcicki; Joel K. Llopiz; Sarah Glancy; Paul E. Caiger; Rene Francolini; Annette Govindarajan; Simon R. Thorrold; Michael Jech; et al. (Frontiers in Marine Science, 2024)
DNA metabarcoding and morphological taxonomic (microscopic) analysis of the gut contents was used to examine diet diversity of seven species of fishes collected from mesopelagic depths (200-1000 m) in the NW Atlantic Ocean Slope Water during Summer 2018 and 2019. Metabarcoding used two gene regions: V9 hypervariable region of nuclear 18S rRNA and mitochondrial cytochrome oxidase I (COI). V9 sequences were classified into 14 invertebrate prey groups, excluding fish due to predator swamping. Ecological network analysis was used to evaluate relative strengths of predator-prey linkages. Multivariate statistical analysis revealed consistently distinct diets of four fish species in 2018 and/or 2019: Argyropelecus aculeatus, Chauliodus sloani, Hygophum hygomii , and Sigmops elongatus . Three other species analyzed ( Malacosteus niger, Nemichthys scolopaceus , and Scopelogadus beanii ) showed more variability between sampling years. COI sequences were classified into eight invertebrate prey groups, within which prey species were detected and identified. Considering all predator species together, a total of 77 prey species were detected with a minimum of 1,000 COI sequences, including 22 copepods, 18 euphausiids, and 7 amphipods. Morphological prey counts were classified into seven taxonomic groups, including a gelatinous group comprised of soft-bodied organisms. The ocean twilight zone or is home to exceptional diversity and biomass of marine fish, which are key players in deep sea food webs. This study used integrative morphological-molecular analysis to provide new insights into trophic relationships and sources of productivity for mesopelagic fishes, including identification of key prey species, recognition of the importance of gelatinous prey, and characterization of differences in diet among fish predators in the NW Atlantic Slope Water.

A sustainable blue economy may not be possible in Tanzania without cutting emissions - Ana M. Queirós; Elizabeth Talbot; Flower E. Msuya; Baraka Kuguru; Narriman Jiddawi; Shigalla Mahongo; Yohana Shaghude; Christopher Muhando; Elias Chundu; Zoe Jacobs; Sevrine Sailley; Elina A. Virtanen; et al. (Science of The Total Environment, 2024)

A new high-resolution Coastal Ice-Ocean Prediction System for the East Coast of Canada - Jean-Philippe Paquin; François Roy; Gregory C. Smith; Sarah MacDermid; Ji Lei; Frédéric Dupont; Youyu Lu; Stephanne Taylor; Simon St-Onge-Drouin; Hauke Blanken; Michael Dunphy; Nancy Soontiens (Ocean Dynamics, 2024)
The Coastal Ice Ocean Prediction System for the East Coast of Canada (CIOPS-E) was developed and implemented operationally at Environment and Climate Change Canada (ECCC) to support a variety of critical marine applications. These include support for ice services, search and rescue, environmental emergency response and maritime safety. CIOPS-E uses a 1/36° horizontal grid (~ 2 km) to simulate sea ice and ocean conditions over the northwest Atlantic Ocean and the Gulf of St. Lawrence (GSL). Forcing at lateral open boundaries is taken from ECCC’s data assimilative Regional Ice-Ocean Prediction System (RIOPS). A spectral nudging method is applied offshore to keep mesoscale features consistent with RIOPS. Over the continental shelf and GSL, the CIOPS-E solution is free to evolve according to the model dynamics. Overall, CIOPS-E significantly improves the representation of tidal and sub-tidal water levels compared to ECCC’s lower resolution systems: RIOPS (~ 6 km) and the Regional Marine Prediction System – GSL (RMPS-GSL, 5 km). Improvements in the GSL are due to the higher resolution and a better representation of bathymetry, boundary forcing and dynamics in the upper St. Lawrence Estuary. Sea surface temperatures show persistent summertime cold bias, larger in CIOPS-E than in RIOPS, as the latter is constrained by observations. The seasonal cycle of sea ice extent and volume, unconstrained in CIOPS-E, compares well with observational estimates, RIOPS and RMPS-GSL. A greater number of fine-scale features are found in CIOPS-E with narrow leads and more intense ice convergence zones, compared to both RIOPS and RMPS-GSL.

Optimising the reintroduction of a specialist peatland butterfly Coenonympha tullia onto peatland restoration sites - Andrew Osborne; Sarah Griffiths; Simon Caporn; Emma Coulthard (Journal of Insect Conservation, 2024)
The two main goals of peatland restoration are habitat improvement and climate change mitigation by reducing greenhouse gas emissions from damaged peatlands and providing a net carbon sink. The biodiversity of specialist peatland species is threatened because of habitat destruction and the large heath butterfly Coenonympha tullia has become a flagship species for peatland ecosystem restoration, with a species reintroduction programme currently underway on a peatland restoration site within Chat Moss, Greater Manchester, UK. The aim of this study was to improve our quantitative understanding of C. tullia habitat resource requirements to optimise habitat restoration for further reintroduction attempts. We monitored butterfly micro-distribution and dispersal during the first three flight seasons (2020, 2021 and 2022) of the reintroduction using high-accuracy GPS, combined with a distance-bearing protocol. Analysis of butterfly flight points and rest points in relation to plant species distribution and abundance, identified the most important habitat resources. Using logistic regression, treatment-response curves were constructed, enabling us to identify critical thresholds for the abundance of these important habitat resources. The break of slope near the top of the logistic curve was identified using segmented regression, giving an estimate of the near-optimal abundance; fourteen Eriophorum vaginatum tussocks per 2 m quadrat and 13.4% Erica tetralix cover. Implications for insect conservation During ecosystem restorations, prior to the reintroduction of species with specialist habitat requirements, it is necessary to have a clear understanding of the abundance of the important habitat resources that need to be provided. The quantitative approach we describe defines the most significant environmental factors and habitat resources, then uses segmented regression to estimate the near-optimal habitat resource requirements; increasing the likelihood of reintroduced populations thriving and reintroduction programmes achieving long-term success.

Exposing illegal hunting and wildlife depletion in the world's largest tropical country through social media data - Hani R. El Bizri; Marcela A. Oliveira; Aline Pessutti Rampini; Simon Knoop; Julia E. Fa; Lauren Coad; Thais Queiroz Morcatty; Gabriel Favero Massocato; Arnaud L. J. Desbiez; João Vitor Campos‐Silva; Daniel Zani La Laina; José Maurício Barbanti Duarte; et al. (Conservation Biology, 2024)
Globally, illegal sport hunting can threaten prey populations when unregulated. Due to its covert nature, illegal sport hunting poses challenges for data collection, hindering efforts to understand the full extent of its impacts. We gathered social media data to analyze patterns of illegal sport hunting and wildlife depletion across Brazil. We collected data for 2 years (2018–2020) across 5 Facebook groups containing posts depicting pictures of illegal sport hunting events of native fauna. We described and mapped these hunting events by detailing the number of hunters involved, the number of species, the mean body mass of individuals, and the number and biomass of individuals hunted per unit area, stratified by Brazilian biome. We also examined the effects of defaunation on hunting yield and composition via regression models, rank–abundance curves, and spatial interpolation. We detected 2046 illegal sport hunting posts portraying the hunting of 4658 animals (∼29 t of undressed meat) across all 27 states and 6 natural biomes of Brazil. Of 157 native species targeted by hunters, 19 are currently threatened with extinction. We estimated that 1414 hunters extracted 3251 kg/million km 2 . Some areas exhibited more pronounced wildlife depletion, in particular the Atlantic Forest and Caatinga biomes. In these areas, there was a shift from large mammals and reptiles to small birds as the main targeted taxa, and biomass extracted per hunting event and mean body mass across all taxonomic groups were lower than in other areas. Our results highlight that illegal sport hunting adds to the pressures of subsistence hunting and the wild meat trade on Brazil's wildlife populations. Enhanced surveillance efforts are needed to reduce illegal sport hunting levels and to develop well‐managed sustainable sport hunting programs. These can support wildlife conservation and offer incentives for local communities to oversee designated sport hunting areas.

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

The Fourth Global Coral Bleaching Event: Where do we go from here? - James Davis Reimer; Raquel S. Peixoto; Sarah W. Davies; Nikki Traylor-Knowles; Morgan L. Short; Rafael A. Cabral-Tena; John A. Burt; Igor Pessoa; Anastazia T. Banaszak; R. Scott Winters; Tom Moore; Verena Schoepf; et al. (Coral Reefs, 2024)

Wheat genetic resources have avoided disease pandemics, improved food security, and reduced environmental footprints: A review of historical impacts and future opportunities - Julie King; Susanne Dreisigacker; Matthew Reynolds; Anindya Bandyopadhyay; Hans‐Joachim Braun; Leonardo Crespo‐Herrera; Jose Crossa; Velu Govindan; Julio Huerta; Maria Itria Ibba; Carlos A. Robles‐Zazueta; Carolina Saint Pierre; et al. (Global Change Biology, 2024)
The use of plant genetic resources (PGR)—wild relatives, landraces, and isolated breeding gene pools—has had substantial impacts on wheat breeding for resistance to biotic and abiotic stresses, while increasing nutritional value, end‐use quality, and grain yield. In the Global South, post‐Green Revolution genetic yield gains are generally achieved with minimal additional inputs. As a result, production has increased, and millions of hectares of natural ecosystems have been spared. Without PGR‐derived disease resistance, fungicide use would have easily doubled, massively increasing selection pressure for fungicide resistance. It is estimated that in wheat, a billion liters of fungicide application have been avoided just since 2000. This review presents examples of successful use of PGR including the relentless battle against wheat rust epidemics/pandemics, defending against diseases that jump species barriers like blast, biofortification giving nutrient‐dense varieties and the use of novel genetic variation for improving polygenic traits like climate resilience. Crop breeding genepools urgently need to be diversified to increase yields across a range of environments (>200 Mha globally), under less predictable weather and biotic stress pressure, while increasing input use efficiency. Given that the ~0.8 m PGR in wheat collections worldwide are relatively untapped and massive impacts of the tiny fraction studied, larger scale screenings and introgression promise solutions to emerging challenges, facilitated by advanced phenomic and genomic tools. The first translocations in wheat to modify rhizosphere microbiome interaction (reducing biological nitrification, reducing greenhouse gases, and increasing nitrogen use efficiency) is a landmark proof of concept. Phenomics and next‐generation sequencing have already elucidated exotic haplotypes associated with biotic and complex abiotic traits now mainstreamed in breeding. Big data from decades of global yield trials can elucidate the benefits of PGR across environments. This kind of impact cannot be achieved without widescale sharing of germplasm and other breeding technologies through networks and public–private partnerships in a pre‐competitive space.

Pharmacokinetic Modeling of the Effect of Tariquidar on Ondansetron Disposition into the Central Nervous System - Manting Chiang; Hyunmoon Back; Jong Bong Lee; Sarah Oh; Tiffany Guo; Simone Girgis; Celine Park; Simon Haroutounian; Leonid Kagan (Pharmaceutical Research, 2024)
Purpose Serotonin (5-HT 3 ) receptor antagonists are promising agents for treatment of neuropathic pain. However, insufficient drug exposure at the central nervous system (CNS) might result in lack of efficacy. The goal of this study was to evaluate the impact of administration of a Pgp inhibitor (tariquidar) on ondansetron exposure in the brain, spinal cord, and cerebrospinal fluid in a wild-type rat model. Methods Ondansetron (10 mg/kg) and tariquidar (7.5 mg/kg) were administered intravenously, plasma and tissue samples were collected and analyzed by HPLC. A mathematical model with brain, spinal cord, cerebrospinal fluid and two systemic disposition compartments was developed to describe the data. Results The results demonstrate that tariquidar at 7.5 mg/kg resulted in a complete inhibition of Pgp efflux of ondansetron in the brain and spinal cord. The compartmental model successfully captured pharmacokinetics of ondansetron in wild type and Pgp knockout (KO) animals receiving the drug alone or in wild type animals receiving the ondansetron and tariquidar combination. Conclusions The study provided important quantitative information on enhancement of CNS exposure to ondansetron using co-administration of Pgp Inhibitor in a rat model, which will be further utilized in conducting a clinical study. Tariquidar co-administration resulted in ondansetron CNS exposure comparable to observed in Pgp KO rats. Results also highlighted the effect of tariquidar on plasma disposition of ondansetron, which may not be dependent on Pgp inhibition, and should be evaluated in future studies.

Early Aboriginal pottery production and offshore island occupation on Jiigurru (Lizard Island group), Great Barrier Reef, Australia - Sean Ulm; Ian J. McNiven; Glenn R. Summerhayes; Pei-hua Wu; Magdalena M.E. Bunbury; Fiona Petchey; Quan Hua; Robert Skelly; Ariana B.J. Lambrides; Cassandra Rowe; Kelsey M. Lowe; Christian H. Reepmeyer; et al. (Quaternary Science Reviews, 2024)

Reading tea leaves worldwide: Decoupled drivers of initial litter decomposition mass‐loss rate and stabilization - Judith M. Sarneel; Mariet M. Hefting; Taru Sandén; Johan van den Hoogen; Devin Routh; Bhupendra S. Adhikari; Juha M. Alatalo; Alla Aleksanyan; Inge H. J. Althuizen; Mohammed H. S. A. Alsafran; Jeff W. Atkins; Laurent Augusto; et al. (Ecology Letters, 2024)
The breakdown of plant material fuels soil functioning and biodiversity. Currently, process understanding of global decomposition patterns and the drivers of such patterns are hampered by the lack of coherent large‐scale datasets. We buried 36,000 individual litterbags (tea bags) worldwide and found an overall negative correlation between initial mass‐loss rates and stabilization factors of plant‐derived carbon, using the Tea Bag Index (TBI). The stabilization factor quantifies the degree to which easy‐to‐degrade components accumulate during early‐stage decomposition (e.g. by environmental limitations). However, agriculture and an interaction between moisture and temperature led to a decoupling between initial mass‐loss rates and stabilization, notably in colder locations. Using TBI improved mass‐loss estimates of natural litter compared to models that ignored stabilization. Ignoring the transformation of dead plant material to more recalcitrant substances during early‐stage decomposition, and the environmental control of this transformation, could overestimate carbon losses during early decomposition in carbon cycle models.

Cryptic diversification, phenotypic plasticity, and host specialization in a sponge-dwelling goby - Ariel Wang; Sarah Yerrace; Luke Tornabene; Simon J. Brandl; Christopher J. Freeman; Carole C. Baldwin; Jordan M. Casey (Coral Reefs, 2024)

Species- or habitat- based assessments of vulnerability to climate change? Informing climate change adaptation in Special Protection Areas for birds in England - Simon J. Duffield; Michael D. Morecroft; James W. Pearce-Higgins; Sarah D. Taylor (Biological Conservation, 2024)

Higher Neuronal Facilitation and Potentiation with APOE4 Suppressed by Angiotensin II - Sarah B. Scheinman; Kuei Y. Tseng; Simon Alford; Leon M. Tai (Molecular Neurobiology, 2024)

Profiles of body image concerns and their associations with disordered eating behaviors - Sarah Baker; Christophe Maïano; Simon A. Houle; Lindsey Nadon; Annie Aimé; Alexandre J.S. Morin (Appetite, 2023)

Auxin and light-mediated regulation of growth, morphogenesis, and alkaloid biosynthesis in Crinum x powellii ‘Album’ callus - Manoj Koirala; Karen Cristine Goncalves dos Santos; Sarah-Eve Gélinas; Simon Ricard; Vahid Karimzadegan; Basanta Lamichhane; Nuwan Sameera Liyanage; Natacha Merindol; Isabel Desgagné-Penix (Phytochemistry, 2023)

Grazing management for soil carbon in Australia: A review - Sarah E. McDonald; Warwick Badgery; Simon Clarendon; Susan Orgill; Katrina Sinclair; Rachelle Meyer; Dominique Bowen Butchart; Richard Eckard; David Rowlings; Peter Grace; Natalie Doran-Browne; Steven Harden; et al. (Journal of Environmental Management, 2023)

Water mixing processes in a complex multi-layer hydrosystem in southwestern Madagascar: a combined isotopic and piezometry approach - Simon D. Carrière; Pascale F. M. Rakotomandrindra; Thomas Heath; Konstantinos Chalikakis; Marina Gillon; Marc Leblanc; Sarah Tweed (Hydrogeology Journal, 2023)
Water transfers through a multilayered aquifer system are difficult to characterize. This study explores whether the conceptual model of water mixing at depth can be extrapolated over a hydrosystem extended across several tens of kilometers and including multiple aquifer layers. The processes are investigated using a combination of isotope tracers and piezometric monitoring over 10 years. The goal of this approach is to better understand how water transfer occurs throughout a complex and poorly documented hydrosystem of the Mahafaly Plateau in southwestern Madagascar. The results show a clear smoothing of isotopic variability with depth, associated with a smoothing of the recharge peaks. Isotopic values are strongly variable in the near surface (from -6.8 to -2.5‰ 18 O) and stabilize at a critical depth (near 20 m) at around -4.7‰ 18 O. These results indicate high vertical flows through the aquifer system, where there is neither obvious dominant recharge via preferential pathways nor lateral mixing. Such a strong smoothing effect on groundwater isotopic variability with depth has been rarely observed so clearly over a large spatial scale. These results provide information on a remote groundwater flow system at a scale pertinent to groundwater resource assessment. The results also indicate that the Neogene aquifers of the Mahafaly Plateau are poorly connected with other water resources (rivers, old sedimentary formations) except for the percolation of water towards the deep Eocene karst. This means that groundwater resources in the Ankazomanga Basin are limited and that it is essential to understand and quantify recharge for sustainable groundwater management.

Persistent headaches one year after bacterial meningitis: prevalence, determinants and impact on quality of life - Rémi Nguyen Van; Sarah Tubiana; Thomas De Broucker; Joseph Cédric; Carine Roy; Marie-Caroline Meyohas; Thierry Prazuck; Catherine Chirouze; Bruno Hoen; Xavier Duval; Matthieu Revest; Bruno Mourvillier; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Simulating carbon accumulation and loss in the central Congo peatlands - Dylan M. Young; Andy J. Baird; Paul J. Morris; Greta C. Dargie; Y. Emmanuel Mampouya Wenina; Mackline Mbemba; Arnoud Boom; Peter Cook; Richard Betts; Eleanor Burke; Yannick E. Bocko; Sarah Chadburn; et al. (Global Change Biology, 2023)
Peatlands of the central Congo Basin have accumulated carbon over millennia. They currently store some 29 billion tonnes of carbon in peat. However, our understanding of the controls on peat carbon accumulation and loss and the vulnerability of this stored carbon to climate change is in its infancy. Here we present a new model of tropical peatland development, DigiBog_Congo, that we use to simulate peat carbon accumulation and loss in a rain‐fed interfluvial peatland that began forming ~20,000 calendar years Before Present (cal. yr BP, where ‘present’ is 1950 CE). Overall, the simulated age‐depth curve is in good agreement with palaeoenvironmental reconstructions derived from a peat core at the same location as our model simulation. We find two key controls on long‐term peat accumulation: water at the peat surface (surface wetness) and the very slow anoxic decay of recalcitrant material. Our main simulation shows that between the Late Glacial and early Holocene there were several multidecadal periods where net peat and carbon gain alternated with net loss. Later, a climatic dry phase beginning ~5200 cal. yr BP caused the peatland to become a long‐term carbon source from ~3975 to 900 cal. yr BP. Peat as old as ~7000 cal. yr BP was decomposed before the peatland's surface became wetter again, suggesting that changes in rainfall alone were sufficient to cause a catastrophic loss of peat carbon lasting thousands of years. During this time, 6.4 m of the column of peat was lost, resulting in 57% of the simulated carbon stock being released. Our study provides an approach to understanding the future impact of climate change and potential land‐use change on this vulnerable store of carbon.

Resource selection by New York City deer reveals the effective interface between wildlife, zoonotic hazards and humans - Meredith C. VanAcker; Vickie L. DeNicola; Anthony J. DeNicola; Sarah Grimké Aucoin; Richard Simon; Katrina L. Toal; Maria A. Diuk‐Wasser; Francesca Cagnacci (Ecology Letters, 2023)
Although the role of host movement in shaping infectious disease dynamics is widely acknowledged, methodological separation between animal movement and disease ecology has prevented researchers from leveraging empirical insights from movement data to advance landscape scale understanding of infectious disease risk. To address this knowledge gap, we examine how movement behaviour and resource utilization by white‐tailed deer ( Odocoileus virginianus ) determines blacklegged tick ( Ixodes scapularis ) distribution, which depend on deer for dispersal in a highly fragmented New York City borough. Multi‐scale hierarchical resource selection analysis and movement modelling provide insight into how deer's movements contribute to the risk landscape for human exposure to the Lyme disease vector– I. scapularis . We find deer select highly vegetated and accessible residential properties which support blacklegged tick survival. We conclude the distribution of tick‐borne disease risk results from the individual resource selection by deer across spatial scales in response to habitat fragmentation and anthropogenic disturbances.

Calibration, validation and testing of a rotational displacement transducer for measuring wheat leaf elongation rates - Simon Dequeker; Sarah Verbeke; Kathy Steppe (Computers and Electronics in Agriculture, 2023)

Grazing livestock move by Lévy walks: Implications for soil health and environment - Alejandro Romero-Ruiz; M. Jordana Rivero; Alice Milne; Sarah Morgan; Paulo Meo Filho; Simon Pulley; Carmen Segura; Paul Harris; Michael RF. Lee; Kevin Coleman; Laura Cardenas; Andrew P. Whitmore (Journal of Environmental Management, 2023)

The Sereine test: Advances towards short and reproducible measurements of a whole building heat transfer coefficient - Sarah Juricic; Mickaël Rabouille; Arnaud Challansonnex; Arnaud Jay; Simon Thébault; Simon Rouchier; Rémi Bouchié (Energy and Buildings, 2023)

Effect of urbanization and parasitism on the gut microbiota of Darwin's finch nestlings - Gabrielle Solomon; Ashley C. Love; Grace J. Vaziri; Johanna Harvey; Taylor Verrett; Kiley Chernicky; Shelby Simons; Lauren Albert; Jaime A. Chaves; Sarah A. Knutie (Molecular Ecology, 2023)
Host‐associated microbiota can be affected by factors related to environmental change, such as urbanization and invasive species. For example, urban areas often affect food availability for animals, which can change their gut microbiota. Invasive parasites can also influence microbiota through competition or indirectly through a change in the host immune response. These interacting factors can have complex effects on host fitness, but few studies have disentangled the relationship between urbanization and parasitism on an organism's gut microbiota. To address this gap in knowledge, we investigated the effects of urbanization and parasitism by the invasive avian vampire fly ( Philornis downsi ) on the gut microbiota of nestling small ground finches ( Geospiza fuliginosa ) on San Cristóbal Island, Galápagos. We conducted a factorial study in which we experimentally manipulated parasite presence in an urban and nonurban area. Faeces were then collected from nestlings to characterize the gut microbiota (i.e. bacterial diversity and community composition). Although we did not find an interactive effect of urbanization and parasitism on the microbiota, we did find main effects of each variable. We found that urban nestlings had lower bacterial diversity and different relative abundances of taxa compared to nonurban nestlings, which could be mediated by introduction of the microbiota of the food items or changes in host physiology. Additionally, parasitized nestlings had lower bacterial richness than nonparasitized nestlings, which could be mediated by a change in the immune system. Overall, this study advances our understanding of the complex effects of anthropogenic stressors on the gut microbiota of birds.

Strengthening global-change science by integrating aeDNA with paleoecoinformatics - John W. Williams; Trisha L. Spanbauer; Peter D. Heintzman; Jessica Blois; Eric Capo; Simon J. Goring; Marie-Eve Monchamp; Laura Parducci; Jordan M. Von Eggers; Inger Greve Alsos; Chris Bowler; Marco J.L. Coolen; et al. (Trends in Ecology & Evolution, 2023)

From behaviour to complex communities: Resilience to anthropogenic noise in a fish-induced trophic cascade - Emilie Rojas; Mélanie Gouret; Simon Agostini; Sarah Fiorini; Paulo Fonseca; Gérard Lacroix; Vincent Médoc (Environmental Pollution, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Identifying Gaps and Challenges in Global Pesticide Legislation that Impact the Protection of Consumer Health: Rice as a Case Study - Patricia Kubiak-Hardiman; Simon A. Haughey; Julie Meneely; Sarah Miller; Kaushik Banerjee; Christopher T. Elliott (Exposure and Health, 2023)
With continued global population expansion, food production will have to increase with crops protected against the growing menace of pests, requiring the increased use of pesticides globally to ensure that agricultural production is optimised and remains economically viable. The aim of this systematic review was to perform an in-depth analysis of pesticide legislation, focusing on rice, to understand the gaps that exist in the harmonisation across different countries. Tricyclazole, carbendazim, thiamethoxam and acephate were considered as these received the highest numbers of RASFF notifications and alerts due to their presence in rice. Global differences in regulations cause trade issues, especially when developing countries use unauthorised pesticides or different MRLs. Discrepancies in the registration and regulation of sales were found to be a global problem. Sales of pesticides and resulting residues in developing countries that are banned in the EU or US is highly concerning. Evidence suggests farmers’ education regarding pesticide use and protection must be increased, particularly as climate change is impacting pesticide use patterns and their bio-efficacy. In conclusion, international pesticide regulations have been implemented to protect consumer health, the environment and facilitate international trade. However, the absence of national MRLs in some countries or non-alignments with Codex MRLs raise significant concerns regarding some pesticides in relation to the protection of consumer health and the use of mixtures versus single pesticides. Additionally, global differences in pesticide regulation highlight problems in trade, especially when developing countries use unauthorised pesticides or when MRLs are not in agreement.

Mineral nutrition in penaeid shrimp - Ha H. Truong; Barney M. Hines; Maurício G. Emerenciano; David Blyth; Sarah Berry; Tansyn H. Noble; Nicholas A. Bourne; Nicholas Wade; Artur N. Rombenso; Cedric J. Simon (Reviews in Aquaculture, 2023)
This review summarises the current knowledge of mineral nutrition for penaeid shrimp. It investigates how the aquatic environment and the lifecycle of shrimp affect requirements and the role that minerals play in shrimp health. Methods of supplying minerals via either water or to feed, and novel ways of supplementing minerals within feed, are discussed. The requirements for individual minerals are summarised with recommendations for minimum levels of dietary inclusion for semi‐intensive and intensive commercial shrimp culture presented where data permits. Estimates of dietary requirement remain broad for most minerals for the main shrimp production species ( Penaeus vannamei , Penaeus monodon and Penaeus japonicus ), with some essential minerals remaining unstudied (Table 2 in Section 5.10). Mineral nutrition will become more important as intensification and diversification of production systems provide new challenges to shrimp aquaculture.

Inconsistent responses of carabid beetles and spiders to land-use intensity and landscape complexity in north-western Europe - Zulin Mei; Jeroen Scheper; Riccardo Bommarco; Gerard Arjen de Groot; Michael P.D. Garratt; Katarina Hedlund; Simon G. Potts; Sarah Redlich; Henrik G. Smith; Ingolf Steffan-Dewenter; Wim H. van der Putten; Stijn van Gils; et al. (Biological Conservation, 2023)

First observations of Weddell seals foraging in sponges in Erebus Bay, Antarctica - Rose T. N. Foster-Dyer; Kimberly T. Goetz; Matthew H. Pinkerton; Takashi Iwata; Rachel R. Holser; Sarah A. Michael; Craig Pritchard; Simon Childerhouse; Jay Rotella; Luisa Federwisch; Daniel P. Costa; Michelle A. LaRue (Polar Biology, 2023)
Attaching cameras to marine mammals allows for first-hand observation of underwater behaviours that may otherwise go unseen. While studying the foraging behaviour of 26 lactating Weddell seals ( Leptonychotes weddellii ) in Erebus Bay during the austral spring of 2018 and 2019, we witnessed three adults and one pup investigating the cavities of Rossellidae glass sponges, with one seal visibly chewing when she removed her head from the sponge. To our knowledge, this is the first report of such behaviour. While the prey item was not identifiable, some Trematomus fish (a known Weddell seal prey) use glass sponges for shelter and in which to lay their eggs. Three of the four sponge foraging observations occurred around 13:00 (NZDT). Two of the three sponge foraging adults had higher-than-average reproductive rates, and the greatest number of previous pups of any seal in our study population, each having ten pups in 12 years. This is far higher than the study population average of three previous pups (± 2.6 SD). This novel foraging strategy may have evolved in response to changes in prey availability, and could offer an evolutionary advantage to some individuals that exploit prey resources that others may not. Our observations offer new insight into the foraging behaviours of one of the world’s most studied marine mammals. Further research on the social aspects of Weddell seal behaviour may increase our understanding of the extent and mechanisms of behavioural transfer between conspecifics. Research into the specific foraging behaviour of especially successful or experienced breeders is also warranted.

Insights from an AIMBE Workshop: Diversifying Paths to Academic Leadership - Beth L. Pruitt; Naomi C. Chesler; Rena Seltzer; Omolola Eniola-Adefeso; Susan S. Margulies; Maritza Salazar Campo; Scott I. Simon; Michele J. Grimm; Sarah Mandell; Andrew Alleyne; Jennifer L. West; Tejal A. Desai (Biomedical Engineering Education, 2023)
The American Institute for Medical and Biological Engineering (AIMBE) hosted a virtual symposium titled “Diversifying Paths to Academic Leadership” on January 27 and 28, 2022. The symposium sought to educate the community on the opportunities for and impact of leadership by biomedical engineering faculty, to encourage and invite women faculty, especially women of color, to consider and prepare to pursue leadership roles, to educate faculty on the expectations and duties of these roles, and to highlight experiences and paths to leadership of women engineering leaders. Here we review the main outcomes of the symposium to provide perspective on (1) personal visioning and positioning for leadership, (2) negotiating for success in leadership positions, and (3) leadership strategies for success specific to women faculty and where applicable, faculty of color.

Anthropogenic petroleum signatures and biodegradation in subantarctic Macquarie Island soils - Sarah B. Houlahan; Ingrid Errington; Grant C. Hose; Catherine K. King; Simon C. George (Chemosphere, 2023)

The Challenge of Global Aflatoxins Legislation with a Focus on Peanuts and Peanut Products: A Systematic Review - Julie P. Meneely; Oluwatobi Kolawole; Simon A. Haughey; Sarah J. Miller; Rudolf Krska; Christopher T. Elliott (Exposure and Health, 2023)
Globally, of all mycotoxins, aflatoxins present a significant threat to human and animal health and has resulted in the introduction of strict food regulatory limits to protect public health. A systematic review, was performed to elucidate the rationale applied in establishing aflatoxin standards and evaluate the economic impacts of these. The focus was peanuts, a principal trading commodity susceptible to aflatoxin contamination. Results revealed that although regulations are established in many countries, there is huge disparity in the maximum limits applied due to different methodologies used when considering exposure assessment. Moreover, in countries most affected by aflatoxin contamination in peanuts, few, if any standards exist. In the case of risk assessments, knowledge gaps identified include the impact of climate change on peanut aflatoxin contamination, the role of aflatoxins in child stunting, Kwashiorkor and immunomodulation and a lack of occurrence and exposure data in many developing countries from contaminated peanuts. Few quantitative studies evaluating the impact of aflatoxin regulations on trade exist and evidence is lacking in terms of what happens to exports that do not meet regulatory requirements. Evidence does suggest a lack of knowledge of the extent of the aflatoxin problem, associated health risks and mitigation strategies in developing countries. A hugely important factor that needs to be highlighted is that while there is a fundamental right for sufficient, safe, nutritious food, in many cases in low-income and lower middle-income countries there exists an incredibly difficult and complex trade-off between food security and food safety.

The role of irradiance in controlling coralline algal calcification - Erik C. Krieger; Wendy A. Nelson; Johan Grand; Eric C. Le Ru; Sarah J. Bury; Amelie Cossais; Simon K. Davy; Christopher E. Cornwall (Limnology and Oceanography, 2023)
Coralline algae are an essential element of benthic ecosystems throughout the ocean's photic zone. Yet, the role of light in shaping the physiology of coralline algae from cold‐water, low‐light habitats is poorly understood. Here, we assess the calcification physiology of five cool temperate coralline algae in response to different irradiance levels over 3 months. We show that in contrast to current models focused on warmer water species, previously observed enhancement of calcification rates by photosynthesis is largely limited to lower irradiances, and that the removal of CO 2 from the calcifying fluid is not the underlying mechanism of this enhancement. Instead, this most likely occurs via two processes: (1) increased ion pumping rates to elevate the calcium carbonate saturation state in the calcifying fluid; and (2) a higher daytime pH in the diffusion boundary layer that raises calcifying fluid pH. However, as irradiance increases, ion pumping becomes increasingly saturated limiting further enhancements. Our results also suggest the existence of two calcification strategies in coralline algae and indicate that magnesium incorporation is determined by the magnesium to calcium ratio in the calcifying fluid ([Mg] CF /[Ca] CF ). This study adds to our mechanistic understanding of calcification in coralline algae and fills in much needed knowledge about the role of light in controlling their physiology.

Synthetic Microfiber Material Influences Ingestion by Freshwater Worms - Sarah A. Martinez; Conner J. Simon; Risa A. Cohen (Bulletin of Environmental Contamination and Toxicology, 2023)

ABCD_Harmonizer: An Open-source Tool for Mapping and Controlling for Scanner Induced Variance in the Adolescent Brain Cognitive Development Study - Jonathan A. Dudley; Thomas C. Maloney; John O. Simon; Gowtham Atluri; Sarah L. Karalunas; Mekibib Altaye; Jeffery N. Epstein; Leanne Tamm (Neuroinformatics, 2023)

SCAview: an Intuitive Visual Approach to the Integrative Analysis of Clinical Data in Spinocerebellar Ataxias - Mischa Uebachs; Philipp Wegner; Sebastian Schaaf; Simon Kugai; Heike Jacobi; Sheng-Han Kuo; Tetsuo Ashizawa; Juliane Fluck; Sophie Tezenas du Montcel; Peter Bauer; Paola Giunti; Arron Cook; et al. (The Cerebellum, 2023)
With SCAview, we present a prompt and comprehensive tool that enables scientists to browse large datasets of the most common spinocerebellar ataxias intuitively and without technical effort. Basic concept is a visualization of data, with a graphical handling and filtering to select and define subgroups and their comparison. Several plot types to visualize all data points resulting from the selected attributes are provided. The underlying synthetic cohort is based on clinical data from five different European and US longitudinal multicenter cohorts in spinocerebellar ataxia type 1, 2, 3, and 6 (SCA1, 2, 3, and 6) comprising > 1400 patients with overall > 5500 visits. First, we developed a common data model to integrate the clinical, demographic, and characterizing data of each source cohort. Second, the available datasets from each cohort were mapped onto the data model. Third, we created a synthetic cohort based on the cleaned dataset. With SCAview, we demonstrate the feasibility of mapping cohort data from different sources onto a common data model. The resulting browser-based visualization tool with a thoroughly graphical handling of the data offers researchers the unique possibility to visualize relationships and distributions of clinical data, to define subgroups and to further investigate them without any technical effort. Access to SCAview can be requested via the Ataxia Global Initiative and is free of charge.

The value of zoos for species and society: The need for a new model - Sarah L. Spooner; Susan L. Walker; Simon Dowell; Andrew Moss (Biological Conservation, 2023)

Targeting de novo loss-of-function variants in constrained disease genes improves diagnostic rates in the 100,000 Genomes Project - Eleanor G. Seaby; N. Simon Thomas; Amy Webb; Helen Brittain; Ana Lisa Taylor Tavares; J. C. Ambrose; P Arumugam; R Bevers; M Bleda; F Boardman-Pretty; C. R. Boustred; H Brittain; et al. (Human Genetics, 2023)
Background Genome sequencing was first offered clinically in the UK through the 100,000 Genomes Project (100KGP). Analysis was restricted to predefined gene panels associated with the patient’s phenotype. However, panels rely on clearly characterised phenotypes and risk missing diagnoses outside of the panel(s) applied. We propose a complementary method to rapidly identify pathogenic variants, including those missed by 100KGP methods. Methods The Loss-of-function Observed/Expected Upper-bound Fraction (LOEUF) score quantifies gene constraint, with low scores correlated with haploinsufficiency. We applied DeNovoLOEUF, a filtering strategy to sequencing data from 13,949 rare disease trios in the 100KGP, by filtering for rare, de novo, loss-of-function variants in disease genes with a LOEUF score < 0.2. We compared our findings with the corresponding patient’s diagnostic reports. Results 324/332 (98%) of the variants identified using DeNovoLOEUF were diagnostic or partially diagnostic (whereby the variant was responsible for some of the phenotype). We identified 39 diagnoses that were “missed” by 100KGP standard analyses, which are now being returned to patients. Conclusion We have demonstrated a highly specific and rapid method with a 98% positive predictive value that has good concordance with standard analysis, low false-positive rate, and can identify additional diagnoses. Globally, as more patients are being offered genome sequencing, we anticipate that DeNovoLOEUF will rapidly identify new diagnoses and facilitate iterative analyses when new disease genes are discovered.

Sex-specific relationships between obesity, physical activity, and gray and white matter volume in cognitively unimpaired older adults - Brittany Intzandt; Safa Sanami; Julia Huck; Anne Labonté; Alexa Pichet Binette; Axel Mathieu; Cynthia Picard; Doris Dea; Claudio Cuello; Alan Evans; Christine Tardif; Gerhard Mulhaup; et al. (GeroScience, 2023)

Association between iron accumulation in the dorsal striatum and compulsive drinking in alcohol use disorder - Haoye Tan; Simon Hubertus; Sebastian Thomas; Alycia M. Lee; Sarah Gerhardt; Martin Fungisai Gerchen; Wolfgang H. Sommer; Falk Kiefer; Lothar Schad; Sabine Vollstädt-Klein (Psychopharmacology, 2023)
Rationale Brain iron accumulation has been observed in neuropsychiatric disorders and shown to be related to neurodegeneration. Objectives In this study, we used quantitative susceptibility mapping (QSM), an emerging MRI technique developed for quantifying tissue magnetic susceptibility, to examine brain iron accumulation in individuals with alcohol use disorder (AUD) and its relation to compulsive drinking. Methods Based on our previous projects, QSM was performed as a secondary analysis with gradient echo sequence images, in 186 individuals with AUD and 274 healthy participants. Whole-brain susceptibility values were calculated with morphology-enabled dipole inversion and referenced to the cerebrospinal fluid. Then, the susceptibility maps were compared between AUD individuals and healthy participants. The relationship between drinking patterns and susceptibility was explored. Results Whole-brain analyses showed that the susceptibility in the dorsal striatum (putamen and caudate) among AUD individuals was higher than healthy participants and was positively related to the Obsessive Compulsive Drinking Scale (OCDS) scores and the amount of drinking in the past three months. Conclusions Increased susceptibility suggests higher iron accumulation in the dorsal striatum in AUD. This surrogate for the brain iron level was linearly associated with the compulsive drinking pattern and the recent amount of drinking, which provides us a new clinical perspective in relation to brain iron accumulation, and also might indicate an association of AUD with neuroinflammation as a consequence of brain iron accumulation. The iron accumulation in the striatum is further relevant for functional imaging studies in AUD by potentially producing signal dropout and artefacts in fMRI images.

Immune dysregulation, polyendocrinopathy and enteropathy, X-linked (IPEX) syndrome due to a mutation in FOXP3, modified by a pathogenic variant in SON (SON DNA-binding protein) - Ranjit I. Kylat; Kelly Stanley; Sarah Simon; Robert P. Erickson (Journal of Applied Genetics, 2023)

Zooplankton‐derived dissolved organic matter composition and its bioavailability to natural prokaryotic communities - Daniele De Corte; Marta M. Varela; Angeles M. Louro; Sarah K. Bercovici; Joaquín Valencia‐Vila; Eva Sintes; Federico Baltar; Tamara Rodríguez‐Ramos; Meinhard Simon; Antonio Bode; Thorsten Dittmar; Jutta Niggemann (Limnology and Oceanography, 2023)
Zooplankton grazing onphytoplankton promotes the release of particulate and dissolved organic matter (DOM) into the water column and therefore plays a key role in organic matter cycling in aquatic systems. Prokaryotes are the main DOM consumers in the ocean by actively remineralizing and transforming it, contributing to its molecular diversification. To explore the molecular composition of zooplankton‐derived DOM and its bioavailability to natural prokaryotic communities, the DOM generated by a mixed zooplankton community in the coastal Atlantic off Spain was used as substrate for a natural prokaryotic community and monitored over a ~ 5‐d incubation experiment. The molecular composition of solid‐phase extracted DOM was characterized via Fourier‐transform ion cyclotron resonance mass spectrometry. After ~ 4 d in the zooplankton‐derived DOM amended incubation, the prokaryotic community demonstrated a 17‐fold exponential increase in cell number. The prokaryotic growth resulted in a reduction in bulk dissolved organic carbon concentration and the zooplankton‐derived DOM was considerably transformed at molecular and bulk elemental levels over the incubation period. The C : N ratio (calculated from the obtained molecular formulae) increased while the functional diversity decreased over the incubation time. In addition, molecular indices pointed to a reduced bioavailability of DOM at the end of the experiment. These findings show that zooplankton excreta are a source of labile organic matter that is quickly metabolized by the prokaryotic community. Therefore, a fraction of carbon is shunted from transfer to secondary consumers similarly to the viral shunt, suggesting that the zooplankton–prokaryotic interactions play an important role in the ocean's carbon cycle.

Potential for redistribution of post‐moult habitat for Eudyptes penguins in the Southern Ocean under future climate conditions - Cara‐Paige Green; David B. Green; Norman Ratcliffe; David Thompson; Mary‐Anne Lea; Alastair M. M. Baylis; Alexander L. Bond; Charles‐André Bost; Sarah Crofts; Richard J. Cuthbert; Jacob González‐Solís; Kyle W. Morrison; et al. (Global Change Biology, 2023)
Anthropogenic climate change is resulting in spatial redistributions of many species. We assessed the potential effects of climate change on an abundant and widely distributed group of diving birds, Eudyptes penguins, which are the main avian consumers in the Southern Ocean in terms of biomass consumption. Despite their abundance, several of these species have undergone population declines over the past century, potentially due to changing oceanography and prey availability over the important winter months. We used light‐based geolocation tracking data for 485 individuals deployed between 2006 and 2020 across 10 of the major breeding locations for five taxa of Eudyptes penguins. We used boosted regression tree modelling to quantify post‐moult habitat preference for southern rockhopper ( E. chrysocome ), eastern rockhopper ( E. filholi ), northern rockhopper ( E. moseleyi ) and macaroni/royal ( E. chrysolophus and E. schlegeli ) penguins. We then modelled their redistribution under two climate change scenarios, representative concentration pathways RCP4.5 and RCP8.5 (for the end of the century, 2071–2100). As climate forcings differ regionally, we quantified redistribution in the Atlantic, Central Indian, East Indian, West Pacific and East Pacific regions. We found sea surface temperature and sea surface height to be the most important predictors of current habitat for these penguins; physical features that are changing rapidly in the Southern Ocean. Our results indicated that the less severe RCP4.5 would lead to less habitat loss than the more severe RCP8.5. The five taxa of penguin may experience a general poleward redistribution of their preferred habitat, but with contrasting effects in the (i) change in total area of preferred habitat under climate change (ii) according to geographic region and (iii) the species (macaroni/royal vs. rockhopper populations). Our results provide further understanding on the regional impacts and vulnerability of species to climate change.

Corrigendum to “Priorities to inform research on marine plastic pollution in Southeast Asia” [Sci. Total Environ. volume 841 (2022) Article 156704] - Lucy C.M. Omeyer; Emily M. Duncan; Kornrawee Aiemsomboon; Nicola Beaumont; Sujaree Bureekul; Bin Cao; Luis R. Carrasco; Suchana Chavanich; James R. Clark; Muhammad R. Cordova; Fay Couceiro; Simon M. Cragg; et al. (Science of The Total Environment, 2023)

Whitening of fire opal: Transformation of silica in soils - Simon Gouzy; Benjamin Rondeau; Pierre Gaudin; Guy Louarn; Carole La; Thierry Lebeau; Vassilissa Vinogradoff; Laura Clodoré; Sarah Chamard-Bois (Chemical Geology, 2023)

The initial phase of the Hönne Valley Reef at Binolen (northern Rhenish Massif, Middle Devonian) - Mieke Löw; Till Söte; Ralph Thomas Becker; Sören Stichling; Andreas May; Zhor Sarah Aboussalam; Simon Felix Zoppe (Palaeobiodiversity and Palaeoenvironments, 2022)
The Hagen-Balve Reef Complex of the northern Rhenish Massif, Germany, is one of the best examples for the globally widespread Givetian to Frasnian reefs. At its eastern end, in the Hönne Valley, it reaches up to 1000 metres in thickness. In general, there is limited knowledge concerning the faunas and palaeoecology of Rhenish initial reef phases. A unique section at Binolen exposes the sharp boundary between the underlying, siliciclastic Upper Honsel Formation and the lower part of the reefal Hagen-Balve Formation. A ca. 14 m thick succession is assigned to the new Binolen Member and investigated in terms of carbonate microfacies, micro-, and macrofaunas. Seven microfacies types ( MF ) characterise a crinoidal coral-stromatoporoid garden setting ( MF-2 to MF-6 ) or allobiostrome of an initial open platform turning upsection into a coral parabiostrome ( MF-7/8 ). The base of the Asbeck Member is locally defined by the appearance of back-reef facies types, such as fenestral limestones ( MF-9 ), which indicate the transformation into a bioherm. Low-diversity conodont faunas prove an influx of open shelf organisms for the Binolen Member and suggest a lower Givetian age (probably Polygnathus timorensis Zone). There are two new Givetian conodont biofacies types characteristic for open biostrome settings, the Bipennatus Biofacies and a Simple Cone Biofacies. Thin sections reveal over 40 different reef builders (rugose and tabulate corals, stromatoporoids, and chaetetid sponges). Around 4200 microfossils from conodont residues consist of agglutinating foraminifers, calcareous sponge spicules (e.g. Heteractinida), scolecodonts, echinoderms (mostly crinoid ossicles and holothurian sclerites), pyritised benthic ostracods, assumed calcified moulds of chitinozoans, subordinate microvertebrates, and other groups. They were analysed quantitatively in order to document changing distribution patterns and environments through time. We distinguish six microfossil-based biofacies types ( BF ), namely the Ostracoda Biofacies ( BF-O ), Foraminifera Biofacies ( BF-F ), Scolecodont Biofacies ( BF-S ), Chitinozoa Biofacies ( BF-C ), Porifera-Scolecodont Biofacies ( BF-PS ), and Porifera-Echinodermata Biofacies ( BF-PE ). Microfacies and microfossil assemblages led to a reconstruction of the local facies development, consisting of seven successive depophases with further subdivisions. At the base, the sudden termination of siliciclastic influx enabled a proliferation of reef builders and microfaunas (Depophase I), followed by a longer deepening phase characterised by exclusive bioclastic wackestones (Depophase II). Depophase III is a short regressive phase with crinoidal coral-stromatoporoid floatstones. Depophase IV is characterised by fluctuations in facies and relative sea-level, which results in three subphases. Depophase V resembles Depophase III, but with argillaceous interbeds and more abundant scolecodonts. It is followed by an interval with coral-stromatoporoid rudstones, which grade into coral-dominated bafflestones of an (auto)parabiostrome (both Depophase VI). Depophase VII represent the back-reef facies, including fenestral pack-bindstones of the basal Asbeck Member. The systematic analysis of reefal microfaunas represents pioneer work that should be tested and expanded to other reefs of the Rhenish Massif and beyond.

Sea to the mountains: quantifying freshwater eel and trout diet reliance on marine subsidies from upstream migrating fish - Simon D. Stewart; Robin Holmes; Yvonne Vadeboncoeur; Sarah J. Bury; Sarah Crump (New Zealand Journal of Marine and Freshwater Research, 2022)
Despite the Southern Hemisphere's high proportion of endemic diadromous fish, the trophic role of upstream migrating forage fish in freshwater ecosystems remains unquantified. We combined food web δ 13 C and δ 15 N analyses with fish biomass estimates to quantify estuarine resource contribution (from the ecologically significant Waituna lagoon) to the diet and growth of the apex predators, longfin eels ( Anguilla dieffenbachii ) and brown trout ( Salmo trutta ) in Waituna Creek, Southland, Aotearoa (New Zealand) during 2019 and 2021. Our results demonstrated that exceptionally high biomasses of large predatory fishes (610–830 kg km −1 ) were maintained in a degraded agricultural catchment through connectivity to a near‐pristine estuarine lagoon. Īnanga ( Galaxias maculatus ) migrating upstream from the lagoon supported 60%–80% of longfin eel and 40%–90% of brown trout biomass over the two years sampled. Mass‐balance modelling suggested that large predatory fish in the Waituna Creek consume about two tonnes of migrating whitebait annually. These findings highlight the wider role of estuarine/marine subsidies in structuring New Zealand freshwater food webs and challenge the orthodoxy of ‘restoring streams from the headwaters down’. Estuarine ecosystems may be more important than headwater areas for sustaining large predatory fish, such as longfin eels, when they are food limited.

Machine learning techniques to characterize functional traits of plankton from image data - Eric C. Orenstein; Sakina‐Dorothée Ayata; Frédéric Maps; Érica C. Becker; Fabio Benedetti; Tristan Biard; Thibault de Garidel‐Thoron; Jeffrey S. Ellen; Filippo Ferrario; Sarah L. C. Giering; Tamar Guy‐Haim; Laura Hoebeke; et al. (Limnology and Oceanography, 2022)
Plankton imaging systems supported by automated classification and analysis have improved ecologists' ability to observe aquatic ecosystems. Today, we are on the cusp of reliably tracking plankton populations with a suite of lab‐based and in situ tools, collecting imaging data at unprecedentedly fine spatial and temporal scales. But these data have potential well beyond examining the abundances of different taxa; the individual images themselves contain a wealth of information on functional traits. Here, we outline traits that could be measured from image data, suggest machine learning and computer vision approaches to extract functional trait information from the images, and discuss promising avenues for novel studies. The approaches we discuss are data agnostic and are broadly applicable to imagery of other aquatic or terrestrial organisms.

Long‐term drivers and timing of accelerated vegetation changes in African biomes and their management implications - Matthew Adesanya Adeleye; Simon Edward Connor; Simon Graeme Haberle; Sarah Ivory; Peter Adegbenga Adeonipekun (Global Ecology and Biogeography, 2022)
Aim Owing to its diverse bioclimatic zones, long human history and intense anthropogenic impacts, Africa provides a model system for studying how global terrestrial ecosystems might respond to accelerated socio‐environmental stress. Africa is particularly vulnerable to climate change and human impact, and insufficient baseline data hamper current environmental management efforts. Using palaeoecological data, we seek to identify the timing, pace and drivers of change in African biomes on a long‐term scale to inform current ecosystem management frameworks on the continent. Location Africa. Time period 0–12 ka. Major taxa studied African biomes. Methods Sixty‐four pollen records across Africa and nearby sites were retrieved from multiple databases/sources and grouped into biomes. Turnover (quantified using the squared chord distance dissimilarity metric) and rarefaction analyses were conducted on pollen records in each biome group to reconstruct regional temporal vegetation turnover and richness. Reconstructed vegetation turnover and richness were compared with independent records of climate, fire and human activity to identify possible drivers of change. Results We found that the most stable biomes were those with the greatest floristic richness. Southern Africa's mediterranean‐type (SAM) ecosystems were the most stable and northern Africa's mediterranean‐type (NAM) ecosystems were the most unstable (mainly owing to fire). Tropical savannas (TS) and SAM ecosystems expressed the most sensitivity to climatic shifts from ≥6 ka, whereas tropical forests (TF) were relatively stable before human activities intensified from c . 2 ka. Floristic richness also declined across the tropics from c . 2 ka. Main conclusions Our analysis pinpoints NAM ecosystems as undergoing the fastest acceleration in turnover on the continent in response to fire, whereas TF and TS have been undergoing unprecedented changes in biodiversity in the last 2,000 years. We expect further changes in biodiversity where climate becomes warmer and drier and where human impacts are novel and rapid in comparison to long‐term baselines.

Improving sightings-derived residency estimation for whale shark aggregations: A novel metric applied to a global data set - Gonzalo Araujo; Ariana Agustines; Steffen S. Bach; Jesse E. M. Cochran; Emilio de la Parra-Galván; Rafael de la Parra-Venegas; Stella Diamant; Alistair Dove; Steve Fox; Rachel T. Graham; Sofia M. Green; Jonathan R. Green; et al. (Frontiers in Marine Science, 2022)
The world’s largest extant fish, the whale shark Rhincodon typus , is one of the most-studied species of sharks globally. The discovery of predictable aggregation sites where these animals gather seasonally or are sighted year-round – most of which are coastal and juvenile-dominated – has allowed for a rapid expansion of research on this species. The most common method for studying whale sharks at these sites is photographic identification (photo-ID). This technique allows for long-term individual-based data to be collected which can, in turn, be used to evaluate population structure, build population models, identify long-distance movements, and assess philopatry and other population dynamics. Lagged identification rate (LIR) models have fewer underlying assumptions than more traditional capture mark recapture approaches, making them more broadly applicable to marine taxa, especially far-ranging megafauna species like whale sharks. However, the increased flexibility comes at a cost. Parameter estimations based on LIR can be difficult to interpret and may not be comparable between areas with different sampling regimes. Using a unique data-set from the Philippines with ~8 years of nearly continuous survey effort, we were able to derive a metric for converting LIR residency estimates into more intuitive days-per-year units. We applied this metric to 25 different sites allowing for the first quantitatively-meaningful comparison of sightings-derived residence among the world’s whale shark aggregations. We validated these results against the only three published acoustic residence metrics (falling within the ranges established by these earlier works in all cases). The results were then used to understand residency behaviours exhibited by the sharks at each site. The adjusted residency metric is an improvement to LIR-based population modelling, already one of the most widely used tools for describing whale shark aggregations. The standardised methods presented here can serve as a valuable tool for assessing residency patterns of whale sharks, which is crucial for tailored conservation action, and can cautiously be tested in other taxa.

Physical processes of summer extreme rainfall interannual variability in Eastern China—part II: evaluation of CMIP6 models - Nicolas Freychet; Simon F. B. Tett; Fangxing Tian; Sihan Li; Buwen Dong; Sarah Sparrow (Climate Dynamics, 2022)
Eastern China is regularly exposed to extreme precipitation with significant socio-economical consequences. Following an observational analysis in a first part of this study, here the ability of the Coupled Model Intercomparison Project Phase 6 models to reproduce the main modes of interannual variability of 5-day summer extreme precipitation over eastern China is evaluated, using an empirical orthogonal teleconnection (EOT) method. These models capture the main patterns and magnitudes of the different EOT patterns, although the North China mode is less well represented. Models also reproduce the dynamical features associated with each mode. There is no systematic improvement in the ability of models to simulate either the pattern or the 5-day intensity when using higher resolution models compared to coarser resolution ones. Instead, multi-member or multi-model ensembles lead to results closer to observations. Using a low mitigation projection pathway (SSP-370), it is shown that the risk of the most extreme 5-day precipitation events by about 40%, 80% and more than 150% for global-mean warming levels, relative to 1850–1900, of + 1.5, + 2 and + 3 $$^{° }$$ ∘ C respectively. This increase is found to be more significant for 5-days events than for seasonal scale precipitation, consistent with previous studies.

Seasonal dynamics of marine protist communities in tidally mixed coastal waters - Mariarita Caracciolo; Fabienne Rigaut‐Jalabert; Sarah Romac; Frédéric Mahé; Samuel Forsans; Jean‐Philippe Gac; Laure Arsenieff; Maxime Manno; Samuel Chaffron; Thierry Cariou; Mark Hoebeke; Yann Bozec; et al. (Molecular Ecology, 2022)
Major seasonal community reorganizations and associated biomass variations are landmarks of plankton ecology. However, the processes of plankton community turnover rates have not been fully elucidated so far. Here, we analyse patterns of planktonic protist community succession in temperate latitudes, based on quantitative taxonomic data from both microscopy counts (cells >10 μm) and ribosomal DNA metabarcoding (size fraction >3 μm, 18S rRNA gene) from plankton samples collected bimonthly over 8 years (2009–2016) at the SOMLIT‐Astan station (Roscoff, Western English Channel). Based on morphology, diatoms were clearly the dominating group all year round and over the study period. Metabarcoding uncovered a wider diversity spectrum and revealed the prevalence of Dinophyceae and diatoms but also of Cryptophyta, Chlorophyta, Cercozoa, Syndiniales and Ciliophora in terms of read counts and or richness. The use of morphological and molecular analyses in combination allowed improving the taxonomic resolution and to identify the sequence of the dominant species and OTUs (18S V4 rDNA‐derived taxa) that drive annual plankton successions. We detected that some of these dominant OTUs were benthic as a result of the intense tidal mixing typical of the French coasts in the English Channel. Our analysis of the temporal structure of community changes point to a strong seasonality and resilience. The temporal structure of environmental variables (especially Photosynthetic Active Radiation, temperature and macronutrients) and temporal structures generated by species life cycles and or species interactions, are key drivers of the observed cyclic annual plankton turnover.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

A Code of Conduct Is Imperative for Ocean Carbon Dioxide Removal Research - Rebecca Loomis; Sarah R. Cooley; James R. Collins; Simon Engler; Lisa Suatoni (Frontiers in Marine Science, 2022)
As the impacts of rising temperatures mount and the global transition to clean energy advances only gradually, scientists and policymakers are looking towards carbon dioxide removal (CDR) methods to prevent the worst impacts of climate change. Attention has increasingly focused on ocean CDR techniques, which enhance or restore marine systems to sequester carbon. Ocean CDR research presents the risk of uncertain impacts to human and environmental welfare, yet there are no domestic regulations aimed at ensuring the safety and efficacy of this research. A code of conduct that establishes principles of responsible research, fairness, and equity is needed in this field. This article presents fifteen key components of an ocean CDR research code of conduct.

Use of modified palm kernel shell particles composite blend with cement or clay as alternative material for block production - Simon Ikechukwu Ichetaonye; Kingsley Kema Ajekwene; Sarah Bill Ulaeto; Moses Ebiowei Yibowei; Ugonna Kingsley Ugo; Tajudeen Olaniyi Adekeye; Chima Kenneth Oguzie (Innovative Infrastructure Solutions, 2022)

Ecological consequences of large herbivore exclusion in an A frican savanna: 12 years of data from the UHURU experiment - Jesse M. Alston; Courtney G. Reed; Leo M. Khasoha; Bianca R. P. Brown; Gilbert Busienei; Nathaniel Carlson; Tyler C. Coverdale; Megan Dudenhoeffer; Marissa A. Dyck; John Ekeno; Abdikadir A. Hassan; Rhianna Hohbein; et al. (Ecology, 2022)
Diverse communities of large mammalian herbivores (LMH), once widespread, are now rare. LMH exert strong direct and indirect effects on community structure and ecosystem functions, and measuring these effects is important for testing ecological theory and for understanding past, current, and future environmental change. This in turn requires long‐term experimental manipulations, owing to the slow and often nonlinear responses of populations and assemblages to LMH removal. Moreover, the effects of particular species or body‐size classes within diverse LMH guilds are difficult to pinpoint, and the magnitude and even direction of these effects often depends on environmental context. Since 2008, we have maintained the Ungulate Herbivory Under Rainfall Uncertainty (UHURU) experiment, a series of size‐selective LMH exclosures replicated across a rainfall/productivity gradient in a semiarid Kenyan savanna. The goals of the UHURU experiment are to measure the effects of removing successively smaller size classes of LMH (mimicking the process of size‐biased extirpation) and to establish how these effects are shaped by spatial and temporal variation in rainfall. The UHURU experiment comprises three LMH‐exclusion treatments and an unfenced control, applied to nine randomized blocks of contiguous 1‐ha plots ( n = 36). The fenced treatments are MEGA (exclusion of megaherbivores, elephant and giraffe), MESO (exclusion of herbivores ≥40 kg), and TOTAL (exclusion of herbivores ≥5 kg). Each block is replicated three times at three sites across the 20‐km rainfall gradient, which has fluctuated over the course of the experiment. The first 5 years of data were published previously ( Ecological Archives E095‐064) and have been used in numerous studies. Since that publication, we have (1) continued to collect data following the original protocols, (2) improved the taxonomic resolution and accuracy of plant and small‐mammal identifications, and (3) begun collecting several new data sets. Here, we present updated and extended raw data from the first 12 years of the UHURU experiment (2008–2019). Data include daily rainfall data throughout the experiment; annual surveys of understory plant communities; annual censuses of woody‐plant communities; annual measurements of individually tagged woody plants; monthly monitoring of flowering and fruiting phenology; every‐other‐month small‐mammal mark–recapture data; and quarterly large‐mammal dung surveys. There are no copyright restrictions; notification of when and how data are used is appreciated and users of UHURU data should cite this data paper when using the data.

Tracing Seal Predation Back to the Source Colony of Their Penguin Prey: A Trace Element and Stable Isotope Analysis - Sarah-Lena Reinhold; Simon D. Goldsworthy; John P.Y. Arnould; Bronwyn M. Gillanders; Sean D. Connell; Rebecca R. McIntosh (Frontiers in Marine Science, 2022)
Marine predators recovering from historic, commercial, over-harvesting can create conservation challenges when they prey on vulnerable species. Pinniped predation of seabirds presents one such challenge and identifying the source colonies experiencing seal predation are needed to inform conservation management and decision planning. Here, we present a novel application of stable isotope and trace element techniques to identify the source colony of little penguins ( Eudyptula minor ) predated by long-nosed fur seals ( Arctocephalus forsteri ). We created baseline biochemical ‘feather-prints’ from feathers for six major breeding colonies across south-east Australia to compare with feathers from predated penguins recovered from seal scats. Feeding trials of captive seals confirmed that digestion of penguin feathers did not compromise stable isotope (δ 13 C and δ 15 N) or trace element (Al, Ti, Sr and Mg) signatures. The resulting biochemical ‘feather-prints’ were found to be robust in being correctly classified to local sites (78%) and broader regions (85%). The distinguishing ‘feather-prints’ appeared to be driven by industrial inputs from land, colony-specific foraging patterns and potentially proximity to oceanographic systems (i.e. upwelling). Here, we show that 46-70% of predated feathers were assigned to ‘local’ penguin colonies. We consider that the regional penguin abundances and the proximity of their colonies to seal sites, as well as demographic-specific foraging patterns may shape their contribution to seal diet at local, regional and inter-regional scales. This diagnostic tool is powerful, having broad applications identifying seabird colonies at greatest risk to pinniped predation and informing targeted, site-specific, conservation effort.

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Wheat genetic loci conferring resistance to stripe rust in the face of genetically diverse races of the fungus Puccinia striiformis f. sp. tritici - Laura Bouvet; Lawrence Percival-Alwyn; Simon Berry; Paul Fenwick; Camila Campos Mantello; Rajiv Sharma; Sarah Holdgate; Ian J. Mackay; James Cockram (Theoretical and Applied Genetics, 2022)
Key message Analysis of a wheat multi-founder population identified 14 yellow rust resistance QTL. For three of the four most significant QTL, haplotype analysis indicated resistance alleles were rare in European wheat. Abstract Stripe rust, or yellow rust (YR), is a major fungal disease of wheat ( Triticum aestivum ) caused by Puccinia striiformis Westend f. sp. tritici ( Pst ). Since 2011, the historically clonal European Pst races have been superseded by the rapid incursion of genetically diverse lineages, reducing the resistance of varieties previously showing durable resistance. Identification of sources of genetic resistance to such races is a high priority for wheat breeding. Here we use a wheat eight-founder multi-parent population genotyped with a 90,000 feature single nucleotide polymorphism array to genetically map YR resistance to such new Pst races. Genetic analysis of five field trials at three UK sites identified 14 quantitative trait loci (QTL) conferring resistance. Of these, four highly significant loci were consistently identified across all test environments, located on chromosomes 1A ( QYr.niab-1A.1 ), 2A ( QYr.niab-2A.1 ), 2B ( QYr.niab-2B.1 ) and 2D ( QYr.niab-2D.1 ), together explaining ~ 50% of the phenotypic variation. Analysis of these four QTL in two-way and three-way combinations showed combinations conferred greater resistance than single QTL, and genetic markers were developed that distinguished resistant and susceptible alleles. Haplotype analysis in a collection of wheat varieties found that the haplotypes associated with YR resistance at three of these four major loci were rare (≤ 7%) in European wheat, highlighting their potential utility for future targeted improvement of disease resistance. Notably, the physical interval for QTL QYr.niab-2B.1 contained five nucleotide-binding leucine-rich repeat candidate genes with integrated BED domains, of which two corresponded to the cloned resistance genes Yr7 and Yr5/YrSp . Graphical abstract

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Do Differences in Latitudinal Distributions of Species and Organelle Haplotypes Reflect Thermal Reaction Norms Within the Emiliania/Gephyrocapsa Complex? - Peter von Dassow; Paula Valentina Muñoz Farías; Sarah Pinon; Esther Velasco-Senovilla; Simon Anguita-Salinas (Frontiers in Marine Science, 2021)
The cosmopolitan phytoplankter Emiliania huxleyi contrasts with its closest relatives that are restricted to narrower latitudinal bands, making it interesting for exploring how alternative outcomes in phytoplankton range distributions arise. Mitochondrial and chloroplast haplogroups within E. huxleyi are shared with their closest relatives: Some E. huxleyi share organelle haplogroups with Gephyrocapsa parvula and G. ericsonii which inhabit lower latitudes, while other E. huxleyi share organelle haplogroups with G. muellerae , which inhabit high latitudes. We investigated whether the phylogeny of E. huxleyi organelles reflects environmental gradients, focusing on the Southeast Pacific where the different haplogroups and species co-occur. There was a high congruence between mitochondrial and chloroplast haplogroups within E. huxleyi . Haplogroup II of E. huxleyi is negatively associated with cooler less saline waters, compared to haplogroup I, both when analyzed globally and across temporal variability at the small special scale of a center of coastal upwelling at 30° S. A new mitochondrial haplogroup Ib detected in coastal Chile was associated with warmer waters. In an experiment focused on inter-species comparisons, laboratory-determined thermal reaction norms were consistent with latitudinal/thermal distributions of species, with G. oceanica exhibiting warm thermal optima and tolerance and G. muellerae exhibiting cooler thermal optima and tolerances. Emiliania huxleyi haplogroups I and II tended to exhibit a wider thermal niche compared to the other Gephyrocapsa , but no differences among haplogroups within E. huxleyi were found. A second experiment, controlling for local adaptation and time in culture, found a significant difference between E. huxleyi haplogroups. The difference between I and II was of the expected sign, but not the difference between I and Ib. The differences were small (≤1°C) compared to differences reported previously within E. huxleyi by local adaptation and even in-culture evolution. Haplogroup Ib showed a narrower thermal niche. The cosmopolitanism of E. huxleyi might result from both wide-spread generalist phenotypes and specialist phenotypes, as well as a capacity for local adaptation. Thermal reaction norm differences can well explain the species distributions but poorly explain distributions among mitochondrial haplogroups within E. huxleyi . Perhaps organelle haplogroup distributions reflect historical rather than selective processes.

Body size and digestive system shape resource selection by ungulates: A cross‐taxa test of the forage maturation hypothesis - Saeideh Esmaeili; Brett R. Jesmer; Shannon E. Albeke; Ellen O. Aikens; Kathryn A. Schoenecker; Sarah R. B. King; Briana Abrahms; Bayarbaatar Buuveibaatar; Jeffrey L. Beck; Randall B. Boone; Francesca Cagnacci; Simon Chamaillé‐Jammes; et al. (Ecology Letters, 2021)
The forage maturation hypothesis (FMH) states that energy intake for ungulates is maximised when forage biomass is at intermediate levels. Nevertheless, metabolic allometry and different digestive systems suggest that resource selection should vary across ungulate species. By combining GPS relocations with remotely sensed data on forage characteristics and surface water, we quantified the effect of body size and digestive system in determining movements of 30 populations of hindgut fermenters (equids) and ruminants across biomes. Selection for intermediate forage biomass was negatively related to body size, regardless of digestive system. Selection for proximity to surface water was stronger for equids relative to ruminants, regardless of body size. To be more generalisable, we suggest that the FMH explicitly incorporate contingencies in body size and digestive system, with small‐bodied ruminants selecting more strongly for potential energy intake, and hindgut fermenters selecting more strongly for surface water.

Compound-Specific Stable Isotope Analysis of Amino Acids in Pelagic Shark Vertebrae Reveals Baseline, Trophic, and Physiological Effects on Bulk Protein Isotope Records - Sarah Magozzi; Simon R. Thorrold; Leah Houghton; Victoria A. Bendall; Stuart Hetherington; Gonzalo Mucientes; Lisa J. Natanson; Nuno Queiroz; Miguel N. Santos; Clive N. Trueman (Frontiers in Marine Science, 2021)
Variations in stable carbon and nitrogen isotope compositions in incremental tissues of pelagic sharks can be used to infer aspects of their spatial and trophic ecology across life-histories. Interpretations from bulk tissue isotopic compositions are complicated, however, because multiple processes influence these values, including variations in primary producer isotope ratios and consumer diets and physiological processing of metabolites. Here we challenge inferences about shark tropho-spatial ecology drawn from bulk tissue isotope data using data for amino acids. Stable isotope compositions of individual amino acids can partition the isotopic variance in bulk tissue into components associated with primary production on the one hand, and diet and physiology on the other. The carbon framework of essential amino acids (EAAs) can be synthesised de novo only by plants, fungi and bacteria and must be acquired by consumers through the diet. Consequently, the carbon isotopic composition of EAAs in consumers reflects that of primary producers in the location of feeding, whereas that of non-essential amino acids (non-EAAs) is additionally influenced by trophic fractionation and isotope dynamics of metabolic processing. We determined isotope chronologies from vertebrae of individual blue sharks and porbeagles from the North Atlantic. We measured carbon and nitrogen isotope compositions in bulk collagen and carbon isotope compositions of amino acids. Despite variability among individuals, common ontogenetic patterns in bulk isotope compositions were seen in both species. However, while life-history movement inferences from bulk analyses for blue sharks were supported by carbon isotope data from essential amino acids, inferences for porbeagles were not, implying that the observed trends in bulk protein isotope compositions in porbeagles have a trophic or physiological explanation, or are suprious effects. We explored variations in carbon isotope compositions of non-essential amino acids, searching for systematic variations that might imply ontogenetic changes in physiological processing, but patterns were highly variable and did not explain variance in bulk protein δ 13 C values. Isotopic effects associated with metabolite processing may overwhelm spatial influences that are weak or inconsistently developed in bulk tissue isotope values, but interpreting mechanisms underpinning isotopic variation in patterns in non-essential amino acids remains challenging.

EurOP2E – the European Open Platform for Prescribing Education, a consensus study among clinical pharmacology and therapeutics teachers - Michiel J. Bakkum; Milan C. Richir; Paraskevi Papaioannidou; Robert Likic; Emilio J. Sanz; Thierry Christiaens; João N. Costa; Romaldas Mačiulaitis; Lorena Dima; Jamie Coleman; Jelle Tichelaar; Michiel A. van Agtmael; et al. (European Journal of Clinical Pharmacology, 2021)
Purpose Sharing and developing digital educational resources and open educational resources has been proposed as a way to harmonize and improve clinical pharmacology and therapeutics (CPT) education in European medical schools. Previous research, however, has shown that there are barriers to the adoption and implementation of open educational resources. The aim of this study was to determine perceived opportunities and barriers to the use and creation of open educational resources among European CPT teachers and possible solutions for these barriers. Methods CPT teachers of British and EU medical schools completed an online survey. Opportunities and challenges were identified by thematic analyses and subsequently discussed in an international consensus meeting. Results Data from 99 CPT teachers from 95 medical schools were analysed. Thirty teachers (30.3%) shared or collaboratively produced digital educational resources. All teachers foresaw opportunities in the more active use of open educational resources, including improving the quality of their teaching. The challenges reported were language barriers, local differences, lack of time, technological issues, difficulties with quality management, and copyright restrictions. Practical solutions for these challenges were discussed and include a peer review system, clear indexing, and use of copyright licenses that permit adaptation of resources. Conclusion Key challenges to making greater use of CPT open educational resources are a limited applicability of such resources due to language and local differences and quality concerns. These challenges may be resolved by relatively simple measures, such as allowing adaptation and translation of resources and a peer review system.

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

Knowledge, attitudes and practices on bovine trypanosomosis control in pastoral and agro pastoral communities surrounding Murchison Falls National Park, Uganda - Daniel Kizza; Michael Ocaido; Anthony Mugisha; Rose Azuba; Sarah Nalule; Howard Onyuth; Simon Peter Musinguzi; Sylvia Nalubwama; Charles Waiswa (Tropical Animal Health and Production, 2021)

A Novel Hybrid Membrane VAD as First Step Toward Hemocompatible Blood Propulsion - Aldo Ferrari; Costanza Giampietro; Björn Bachmann; Laura Bernardi; Deon Bezuidenhhout; Paolo Ermanni; Raoul Hopf; Sarah Kitz; Gerald Kress; Christian Loosli; Vita Marina; Mirko Meboldt; et al. (Annals of Biomedical Engineering, 2021)
Heart failure is a raising cause of mortality. Heart transplantation and ventricular assist device (VAD) support represent the only available lifelines for end stage disease. In the context of donor organ shortage, the future role of VAD as destination therapy is emerging. Yet, major drawbacks are connected to the long-term implantation of current devices. Poor VAD hemocompatibility exposes the patient to life-threatening events, including haemorrhagic syndromes and thrombosis. Here, we introduce a new concept of artificial support, the Hybrid Membrane VAD, as a first-of-its-kind pump prototype enabling physiological blood propulsion through the cyclic actuation of a hyperelastic membrane, enabling the protection from the thrombogenic interaction between blood and the implant materials. The centre of the luminal membrane surface displays a rationally-developed surface topography interfering with flow to support a living endothelium. The precast cell layer survives to a range of dynamically changing pump actuating conditions i.e., actuation frequency from 1 to 4 Hz, stroke volume from 12 to 30 mL, and support duration up to 313 min, which are tested both in vitro and in vivo , ensuring the full retention of tissue integrity and connectivity under challenging conditions. In summary, the presented results constitute a proof of principle for the Hybrid Membrane VAD concept and represent the basis for its future development towards clinical validation.

Phenological mismatch between breeding birds and their surveyors and implications for estimating population trends - Dario Massimino; Sarah J. Harris; Simon Gillings (Journal of Ornithology, 2021)

Trawl fishing impacts on the status of seabed fauna in diverse regions of the globe - Tessa Mazor; C. Roland Pitcher; Wayne Rochester; Michel J. Kaiser; Jan G. Hiddink; Simon Jennings; Ricardo Amoroso; Robert A. McConnaughey; Adriaan D. Rijnsdorp; Ana M. Parma; Petri Suuronen; Jeremy Collie; et al. (Fish and Fisheries, 2021)
Bottom trawl fishing is a controversial activity. It yields about a quarter of the world's wild seafood, but also has impacts on the marine environment. Recent advances have quantified and improved understanding of large‐scale impacts of trawling on the seabed. However, such information needs to be coupled with distributions of benthic invertebrates (benthos) to assess whether these populations are being sustained under current trawling regimes. This study collated data from 13 diverse regions of the globe spanning four continents. Within each region, we combined trawl intensity distributions and predicted abundance distributions of benthos groups with impact and recovery parameters for taxonomic classes in a risk assessment model to estimate benthos status. The exposure of 220 predicted benthos‐group distributions to trawling intensity (as swept area ratio) ranged between 0% and 210% (mean = 37%) of abundance. However, benthos status, an indicator of the depleted abundance under chronic trawling pressure as a proportion of untrawled state, ranged between 0.86 and 1 (mean = 0.99), with 78% of benthos groups > 0.95. Mean benthos status was lowest in regions of Europe and Africa, and for taxonomic classes Bivalvia and Gastropoda. Our results demonstrate that while spatial overlap studies can help infer general patterns of potential risk, actual risks cannot be evaluated without using an assessment model that incorporates trawl impact and recovery metrics. These quantitative outputs are essential for sustainability assessments, and together with reference points and thresholds, can help managers ensure use of the marine environment is sustainable under the ecosystem approach to management.

Pharmacokinetic Modeling of the Impact of P-glycoprotein on Ondansetron Disposition in the Central Nervous System - Manting Chiang; Hyun-moon Back; Jong Bong Lee; Sarah Oh; Tiffany Guo; Simone Girgis; Celine Park; Simon Haroutounian; Leonid Kagan (Pharmaceutical Research, 2020)

Joint Multi-modal Parcellation of the Human Striatum: Functions and Clinical Relevance - Xiaojin Liu; Simon B. Eickhoff; Felix Hoffstaedter; Sarah Genon; Svenja Caspers; Kathrin Reetz; Imis Dogan; Claudia R. Eickhoff; Ji Chen; Julian Caspers; Niels Reuter; Christian Mathys; et al. (Neuroscience Bulletin, 2020)

Evaluation of the arachidonic acid pathway in bipolar disorder: a systematic review - Daniela V. Bavaresco; Maria Laura R. Uggioni; Carla S. Simon; Tamy Colonetti; Sarah D. Ferraz; Mateus V. B. Cruz; Samira S. Valvassori; João Quevedo; Maria Inês da Rosa (Molecular Biology Reports, 2020)

Effect of introduced parasites on the survival and microbiota of nestling cactus finches (Geospiza scandens) in the Galápagos Islands - Alyssa M. Addesso; Johanna A. Harvey; Grace J. Vaziri; Taylor B. Verrett; Lauren Albert; Corinne Arthur; Kiley Chernicky; Shelby R. Simons; Jaime Chaves; Sarah A. Knutie (Journal of Ornithology, 2020)

Differences in cohort study data affect external validation of artificial intelligence models for predictive diagnostics of dementia - lessons for translation into clinical practice - Colin Birkenbihl; Mohammad Asif Emon; Henri Vrooman; Sarah Westwood; Simon Lovestone; Martin Hofmann-Apitius; Holger Fröhlich (EPMA Journal, 2020)
Artificial intelligence (AI) approaches pose a great opportunity for individualized, pre-symptomatic disease diagnosis which plays a key role in the context of personalized, predictive, and finally preventive medicine (PPPM). However, to translate PPPM into clinical practice, it is of utmost importance that AI-based models are carefully validated. The validation process comprises several steps, one of which is testing the model on patient-level data from an independent clinical cohort study. However, recruitment criteria can bias statistical analysis of cohort study data and impede model application beyond the training data. To evaluate whether and how data from independent clinical cohort studies differ from each other, this study systematically compares the datasets collected from two major dementia cohorts, namely, the Alzheimer’s Disease Neuroimaging Initiative (ADNI) and AddNeuroMed. The presented comparison was conducted on individual feature level and revealed significant differences among both cohorts. Such systematic deviations can potentially hamper the generalizability of results which were based on a single cohort dataset. Despite identified differences, validation of a previously published, ADNI trained model for prediction of personalized dementia risk scores on 244 AddNeuroMed subjects was successful: External validation resulted in a high prediction performance of above 80% area under receiver operator characteristic curve up to 6 years before dementia diagnosis. Propensity score matching identified a subset of patients from AddNeuroMed, which showed significantly smaller demographic differences to ADNI. For these patients, an even higher prediction performance was achieved, which demonstrates the influence systematic differences between cohorts can have on validation results. In conclusion, this study exposes challenges in external validation of AI models on cohort study data and is one of the rare cases in the neurology field in which such external validation was performed. The presented model represents a proof of concept that reliable models for personalized predictive diagnostics are feasible, which, in turn, could lead to adequate disease prevention and hereby enable the PPPM paradigm in the dementia field.

To Fish or Not to Fish – Economic Perspectives of the Pelagic Northeast Atlantic Mackerel and Herring Fishery - Sandra Rybicki; Katell G. Hamon; Sarah Simons; Axel Temming (Frontiers in Marine Science, 2020)

Thioredoxin System Protein Expression Is Associated with Poor Clinical Outcome in Adult and Paediatric Gliomas and Medulloblastomas - Anqi Yao; Sarah J. Storr; Khaled Al-hadyan; Ruman Rahman; Stuart Smith; Richard Grundy; Simon Paine; Stewart G. Martin (Molecular Neurobiology, 2020)
The thioredoxin (Trx) system is an important enzyme family that regulates cellular redox homeostasis. Protein expression of Trx system family members has been assessed in various cancers and linked to various clinicopathological variables, disease progression, treatment response and survival outcomes but information is lacking in brain tumours. Expression of the system was therefore examined, by immunohistochemistry in different brain tumour types, adult and paediatric cases, to determine if expression was of importance to clinical outcome. Trx system proteins were expressed, to variable levels, across all brain tumour types with significant variations in expression between different tumour types/grades/regions. High Trx reductase (TrxR) expression was linked to worse prognosis across all cohorts. High cytoplasmic TrxR expression was significantly associated with adverse overall survival (OS) in adult glioblastoma ( P = 0.027) and paediatric low-grade glioma (LGG) patients ( P = 0.012). High expression of nuclear TrxR, cytoplasmic and nuclear Trx and Trx-interacting protein (TxNIP) was associated with improved OS in paediatric LGGs ( P = 0.031, P < 0.001, P = 0.044 and P = 0.018, respectively). For patients with high-grade gliomas, both high cytoplasmic TrxR and Trx expression were associated with poor OS ( P = 0.002 and P = 0.007, respectively). In medulloblastoma, high expression of cytoplasmic TrxR and Trx and nuclear Trx was associated with worse prognosis ( P = 0.013, P = 0.033 and P = 0.007, respectively); with cytoplasmic TrxR and nuclear Trx remaining so in multivariate analysis ( P = 0.009 and P = 0.013, respectively). The consistent finding that high levels of cytoplasmic TrxR are associated with a worse prognosis across all cohorts suggests that TrxR is an important therapeutic target in brain cancers.

Prescription medicines with potential for foetal harm: dispensing before and during pregnancy in New Zealand, 2005–2015 - Sarah Donald; Katrina Sharples; David Barson; Simon Horsburgh; Lianne Parkin (European Journal of Clinical Pharmacology, 2020)

CBPtools: a Python package for regional connectivity-based parcellation - Niels Reuter; Sarah Genon; Shahrzad Kharabian Masouleh; Felix Hoffstaedter; Xiaojin Liu; Tobias Kalenscher; Simon B. Eickhoff; Kaustubh R. Patil (Brain Structure and Function, 2020)
Regional connectivity-based parcellation (rCBP) is a widely used procedure for investigating the structural and functional differentiation within a region of interest (ROI) based on its long-range connectivity. No standardized software or guidelines currently exist for applying rCBP, making the method only accessible to those who develop their own tools. As such, there exists a discrepancy between the laboratories applying the procedure each with their own software solutions, making it difficult to compare and interpret the results. Here, we outline an rCBP procedure accompanied by an open source software package called CBPtools . CBPtools is a Python (version 3.5+) package that allows users to run an extensively evaluated rCBP analysis workflow on a given ROI. It currently supports two modalities: resting-state functional connectivity and structural connectivity based on diffusion-weighted imaging, along with support for custom connectivity matrices. Analysis parameters are customizable and the workflow can be scaled to a large number of subjects using a parallel processing environment. Parcellation results with corresponding validity metrics are provided as textual and graphical output. Thus, CBPtools provides a simple plug-and-play, yet customizable way to conduct rCBP analyses. By providing an open-source software we hope to promote reproducible and comparable rCBP analyses and, importantly, make the rCBP procedure readily available. Here, we demonstrate the utility of CBPtools using a voluminous data set on an average compute-cluster infrastructure by performing rCBP on three ROIs prominently featured in parcellation literature.

P38 MAPK and glucocorticoid receptor crosstalk in bronchial epithelial cells - Simon Lea; Jian Li; Jonathan Plumb; Kate Gaffey; Sarah Mason; Rosie Gaskell; Chris Harbron; Dave Singh (Journal of Molecular Medicine, 2020)
p38 MAPK inhibition may have additive and synergistic anti-inflammatory effects when used with corticosteroids. We investigated crosstalk between p38 MAPK inhibitors and corticosteroids in bronchial epithelial cells to investigate synergistic effects on cytokine production and the molecular mechanisms involved. Effects of the p38 MAPK inhibitor BIRB-796 and dexamethasone alone and in combination on LPS, polyI:C or TNFα -induced IL-6, CXCL8 and RANTES were assessed in 16HBEs (human epithelial cell line) and on TNFα-induced IL-6 and CXCL8 in primary human epithelial cells from asthma patients and healthy controls. 16HBEs were used to assess effects of BIRB-796 alone and in combination with dexamethasone on glucocorticoid receptor (GR) activity by reporter gene assay, expression of GR target genes and nuclear localisation using Western blot. The effects of BIRB-796 on TNFα stimulated phosphorylation of p38 MAPK and GR at serine (S) 226 by Western blot. Epithelial levels of phosphorylated p38 MAPK and GR S226 were determined by immunohistochemistry in bronchial biopsies from asthma patients and healthy controls. BIRB-796 in combination with dexamethasone increased inhibition of cytokine production in a synergistic manner. Combination treatment significantly increased GR nuclear localisation compared to dexamethasone alone. BIRB-796 inhibited TNFα-induced p38 MAPK and GR S226 phosphorylation. Phosphorylated GR S226 and p38 MAPK levels were increased in bronchial epithelium of more severe asthma patients. Molecular crosstalk exists between p38 MAPK activation and GR function in human bronchial epithelial cells, which alters GR activity. Combining a p38 MAPK inhibitor and a corticosteroid may demonstrate therapeutic potential in severe asthma . Key messages • Combination of corticosteroid and p38 inhibitor in human bronchial epithelial cells • Combination increased cytokine inhibition synergistically and nuclear GR • p38 MAPK inhibition reduced TNFα-induced phosphorylation of GR at S226 but not S211 • Phosphorylated GRS226 and p38 is increased in bronchial epithelium in severe asthma • Combining a p38 inhibitor and a corticosteroid may be effective in asthma treatment

Skin Filling and Firming Activity of a Hyaluronic Acid Inducing Synthetic Tripeptide - Remo Campiche; Eileen Jackson; Guillaume Laurent; Magalie Roche; Sarah Gougeon; Pierre Séroul; Simon Ströbel; Marco Massironi; Mathias Gempeler (International Journal of Peptide Research and Therapeutics, 2020)

PelagiCam: a novel underwater imaging system with computer vision for semi-automated monitoring of mobile marine fauna at offshore structures - Emma V. Sheehan; Danielle Bridger; Sarah J. Nancollas; Simon J. Pittman (Environmental Monitoring and Assessment, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Examining Resources, Initiatives, and Regulatory Pathways to Advance Regenerative Medicine Manufacturing - Joshua Hunsberger; Martha S. Lundberg; Julie Allickson; Carl G. Simon; Claudia Zylberberg; Sarah H. Beachy (Current Stem Cell Reports, 2019)

Effects of Mineral Nitrogen Partitioning on Tree–Grass Coexistence in West African Savannas - Sarah Konaré; Simon Boudsocq; Jacques Gignoux; Jean-Christophe Lata; Xavier Raynaud; Sébastien Barot (Ecosystems, 2019)

Estimating aboveground net biomass change for tropical and subtropical forests: Refinement of IPCC default rates using forest plot data - Daniela Requena Suarez; Danaë M. A. Rozendaal; Veronique De Sy; Oliver L. Phillips; Esteban Alvarez‐Dávila; Kristina Anderson‐Teixeira; Alejandro Araujo‐Murakami; Luzmila Arroyo; Timothy R. Baker; Frans Bongers; Roel J. W. Brienen; Sarah Carter; et al. (Global Change Biology, 2019)
As countries advance in greenhouse gas (GHG) accounting for climate change mitigation, consistent estimates of aboveground net biomass change (∆AGB) are needed. Countries with limited forest monitoring capabilities in the tropics and subtropics rely on IPCC 2006 default ∆AGB rates, which are values per ecological zone, per continent. Similarly, research into forest biomass change at a large scale also makes use of these rates. IPCC 2006 default rates come from a handful of studies, provide no uncertainty indications and do not distinguish between older secondary forests and old‐growth forests. As part of the 2019 Refinement to the 2006 IPCC Guidelines for National Greenhouse Gas Inventories, we incorporate ∆AGB data available from 2006 onwards, comprising 176 chronosequences in secondary forests and 536 permanent plots in old‐growth and managed/logged forests located in 42 countries in Africa, North and South America and Asia. We generated ∆AGB rate estimates for younger secondary forests (≤20 years), older secondary forests (>20 years and up to 100 years) and old‐growth forests, and accounted for uncertainties in our estimates. In tropical rainforests, for which data availability was the highest, our ∆AGB rate estimates ranged from 3.4 (Asia) to 7.6 (Africa) Mg ha −1 year −1 in younger secondary forests, from 2.3 (North and South America) to 3.5 (Africa) Mg ha −1 year −1 in older secondary forests, and 0.7 (Asia) to 1.3 (Africa) Mg ha −1 year −1 in old‐growth forests. We provide a rigorous and traceable refinement of the IPCC 2006 default rates in tropical and subtropical ecological zones, and identify which areas require more research on ∆AGB. In this respect, this study should be considered as an important step towards quantifying the role of tropical and subtropical forests as carbon sinks with higher accuracy; our new rates can be used for large‐scale GHG accounting by governmental bodies, nongovernmental organizations and in scientific research.

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

Correction to: PyPNS: Multiscale Simulation of a Peripheral Nerve in Python - Carl H. Lubba; Yann Le Guen; Sarah Jarvis; Nick S. Jones; Simon C. Cork; Amir Eftekhar; Simon R. Schultz (Neuroinformatics, 2019)

Deconstructing compassionate conservation - Matt W. Hayward; Alex Callen; Benjamin L. Allen; Guy Ballard; Femke Broekhuis; Cassandra Bugir; Rohan H. Clarke; John Clulow; Simon Clulow; Jennifer C. Daltry; Harriet T. Davies‐Mostert; Peter J. S. Fleming; et al. (Conservation Biology, 2019)
Compassionate conservation focuses on 4 tenets: first, do no harm; individuals matter; inclusivity of individual animals; and peaceful coexistence between humans and animals. Recently, compassionate conservation has been promoted as an alternative to conventional conservation philosophy. We believe examples presented by compassionate conservationists are deliberately or arbitrarily chosen to focus on mammals; inherently not compassionate; and offer ineffective conservation solutions. Compassionate conservation arbitrarily focuses on charismatic species, notably large predators and megaherbivores. The philosophy is not compassionate when it leaves invasive predators in the environment to cause harm to vastly more individuals of native species or uses the fear of harm by apex predators to terrorize mesopredators. Hindering the control of exotic species (megafauna, predators) in situ will not improve the conservation condition of the majority of biodiversity. The positions taken by so‐called compassionate conservationists on particular species and on conservation actions could be extended to hinder other forms of conservation, including translocations, conservation fencing, and fertility control. Animal welfare is incredibly important to conservation, but ironically compassionate conservation does not offer the best welfare outcomes to animals and is often ineffective in achieving conservation goals. Consequently, compassionate conservation may threaten public and governmental support for conservation because of the limited understanding of conservation problems by the general public.

Constraining Southern Ocean Air-Sea-Ice Fluxes Through Enhanced Observations - Sebastiaan Swart; Sarah T. Gille; Bruno Delille; Simon Josey; Matthew Mazloff; Louise Newman; Andrew F. Thompson; Jim Thomson; Brian Ward; Marcel D. du Plessis; Elizabeth C. Kent; James Girton; et al. (Frontiers in Marine Science, 2019)

Air-Sea Fluxes With a Focus on Heat and Momentum - Meghan F. Cronin; Chelle L. Gentemann; James Edson; Iwao Ueki; Mark Bourassa; Shannon Brown; Carol Anne Clayson; Chris W. Fairall; J. Thomas Farrar; Sarah T. Gille; Sergey Gulev; Simon A. Josey; et al. (Frontiers in Marine Science, 2019)

Systemic Exposure of Rituximab Increased by Ibrutinib: Pharmacokinetic Results and Modeling Based on the HELIOS Trial - Silvia Maria Lavezzi; Jan de Jong; Martine Neyens; Paula Cramer; Fatih Demirkan; Graeme Fraser; Nancy Bartlett; Marie-Sarah Dilhuydy; Javier Loscertales; Abraham Avigdor; Simon Rule; Olga Samoilova; et al. (Pharmaceutical Research, 2019)

Coupling between taxonomic and functional diversity in protistan coastal communities - Pierre Ramond; Marc Sourisseau; Nathalie Simon; Sarah Romac; Sophie Schmitt; Fabienne Rigaut‐Jalabert; Nicolas Henry; Colomban de Vargas; Raffaele Siano (Environmental Microbiology, 2019)
Summary The study of protistan functional diversity is crucial to understand the dynamics of oceanic ecological processes. We combined the metabarcoding data of various coastal ecosystems and a newly developed trait‐based approach to study the link between taxonomic and functional diversity across marine protistan communities of different size‐classes. Environmental DNA was extracted and the V4 18S rDNA genomic region was amplified and sequenced. In parallel, we tried to annotate the operational taxonomic units (OTUs) from our metabarcoding dataset to 30 biological traits using published and accessible information on protists. We then developed a method to study trait correlations across protists (i.e. trade‐offs) in order to build the best functional groups. Based on the annotated OTUs and our functional groups, we demonstrated that the functional diversity of marine protist communities varied in parallel with their taxonomic diversity. The coupling between functional and taxonomic diversity was conserved across different protist size classes. However, the smallest size‐fraction was characterized by wider taxonomic and functional groups diversity, corroborating the idea that nanoplankton and picoplankton are part of a more stable ecological background on which larger protists and metazoans might develop.

PyPNS: Multiscale Simulation of a Peripheral Nerve in Python - Carl H. Lubba; Yann Le Guen; Sarah Jarvis; Nick S. Jones; Simon C. Cork; Amir Eftekhar; Simon R. Schultz (Neuroinformatics, 2019)
Bioelectronic Medicines that modulate the activity patterns on peripheral nerves have promise as a new way of treating diverse medical conditions from epilepsy to rheumatism. Progress in the field builds upon time consuming and expensive experiments in living organisms. To reduce experimentation load and allow for a faster, more detailed analysis of peripheral nerve stimulation and recording, computational models incorporating experimental insights will be of great help. We present a peripheral nerve simulator that combines biophysical axon models and numerically solved and idealised extracellular space models in one environment. We modelled the extracellular space as a three-dimensional resistive continuum governed by the electro-quasistatic approximation of the Maxwell equations. Potential distributions were precomputed in finite element models for different media (homogeneous, nerve in saline, nerve in cuff) and imported into our simulator. Axons, on the other hand, were modelled more abstractly as one-dimensional chains of compartments. Unmyelinated fibres were based on the Hodgkin-Huxley model; for myelinated fibres, we adapted the model proposed by McIntyre et al. in 2002 to smaller diameters. To obtain realistic axon shapes, an iterative algorithm positioned fibres along the nerve with a variable tortuosity fit to imaged trajectories. We validated our model with data from the stimulated rat vagus nerve. Simulation results predicted that tortuosity alters recorded signal shapes and increases stimulation thresholds. The model we developed can easily be adapted to different nerves, and may be of use for Bioelectronic Medicine research in the future.

Signatures of genetic adaptation to extremely varied Australian environments in introduced European house sparrows - Samuel C. Andrew; Henrik Jensen; Ingerid J. Hagen; Sarah Lundregan; Simon C. Griffith (Molecular Ecology, 2018)
Due to its history of multiple introductions to novel environments worldwide, the house sparrow has been used as a model species to study local adaption in invasive avian species. New genomic resources such as a custom 200K SNP array and a house sparrow reference genome provide great prospects for studying rapid local adaptation in this invasive species. Here, we analyse high‐density genomewide genetic data collected across an extensive range of temperate, arid and tropical climates, in Australian populations that were introduced from Europe 150 years ago. We used two population differentiation ( PD ) and two ecological association ( EA ) methods to identify putative loci subject to selection across these varied climates. A majority of the outlier SNP s were identified through the use of the latent factor mixed models ( LFMM ) EA method, but the BayeScEnv EA method had the strongest overlap with the outliers from the two PD methods. Out of all the 971 outliers identified across the different methods, 38.3% were physically linked (within 20 kbps) to 575 known protein‐coding regions in the house sparrow reference genome. Interestingly, some outlier genes had been previously identified in genome scan studies of broadly distributed species or had strong links to traits that are expected to be important to local adaptation, for example, heat‐shock proteins, immune response and HOX genes. However, many outliers still have unknown relevance and some outliers can be false positives. Our results identify an opportunity to use the house sparrow model to further study local adaptation in an invasive species.

Ecology can inform genetics: Disassortative mating contributes to MHC polymorphism in Leach’s storm‐petrels ( Oceanodroma leucorhoa ) - Brian Hoover; Miguel Alcaide; Sarah Jennings; Simon Yung Wa Sin; Scott V. Edwards; Gabrielle A. Nevitt (Molecular Ecology, 2018)
Studies of MHC‐based mate choice in wild populations often test hypotheses on species exhibiting female choice and male–male competition, which reflects the general prevalence of females as the choosy sex in natural systems. Here, we examined mutual mate‐choice patterns in a small burrow‐nesting seabird, the Leach’s storm‐petrel ( Oceanodroma leucorhoa ), using the major histocompatibility complex (MHC). The life history and ecology of this species are extreme: both partners work together to fledge a single chick during the breeding season, a task that requires regularly travelling hundreds of kilometres to and from foraging grounds over a 6‐ to 8‐week provisioning period. Using a 5‐year data set unprecedented for this species ( n = 1078 adults and 925 chicks), we found a positive relationship between variation in the likelihood of female reproductive success and heterozygosity at Ocle‐ DAB 2, a MHC class IIB locus. Contrary to previous reports rejecting disassortative mating as a mechanism for maintaining genetic polymorphism in this species, here we show that males make significant disassortative mate‐choice decisions. Variability in female reproductive success suggests that the most common homozygous females (Ocle‐ DAB 2*01/Ocle‐ DAB 2*01) may be physiologically disadvantaged and, therefore, less preferred as lifelong partners for choosy males. The results from this study support the role of mate choice in maintaining high levels of MHC variability in a wild seabird species and highlight the need to incorporate a broader ecological framework and sufficient sample sizes into studies of MHC ‐based mating patterns in wild populations in general.

Author Correction: Impacts of elevated atmospheric CO2 concentration on terrestrial-aquatic carbon transfer and a downstream aquatic microbial community - Emma Rochelle-Newall; Audrey Niboyet; Ludwig Jardillier; Sarah Fiorini; Simon Chollet; Mathieu Llavata; Elisa de Santis; Sébastien Barot; Gérard Lacroix (Aquatic Sciences, 2018)

Impacts of elevated atmospheric CO2 concentration on terrestrial-aquatic carbon transfer and a downstream aquatic microbial community - Emma Rochelle-Newall; Audrey Niboyet; Ludwig Jardiller; Sarah Fiorini; Simon Chollet; Mathieu Llavata; Elisa de Santis; Sébastien Barot; Gérard Lacroix (Aquatic Sciences, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Genetic diversity through time and space: diversity and demographic history from natural history specimens and serially sampled contemporary populations of the threatened Gouldian finch (Erythrura gouldiae) - Peri E. Bolton; Lee A. Rollins; James Brazill-Boast; Kimberley L. Maute; Sarah Legge; Jeremy J. Austin; Simon C. Griffith (Conservation Genetics, 2018)

Incongruence in molecular species delimitation schemes: What to do when adding more data is difficult - Sarah J. Jacobs; Casey Kristofferson; Simon Uribe‐Convers; Maribeth Latvis; David C. Tank (Molecular Ecology, 2018)
Using multiple, independent approaches to molecular species delimitation is advocated to accommodate limitations and assumptions of a single approach. Incongruence in delimitation schemes is a potential by‐product of employing multiple methods on the same data, and little attention has been paid to its reconciliation. Instead, a particular scheme is prioritized, and/or molecular delimitations are coupled with additional, independent lines of evidence that mitigate incongruence. We advocate that incongruence within a line of evidence should be accounted for before comparing across lines of evidence that can themselves be incongruent. Additionally, it is not uncommon for empiricists working in nonmodel systems to be data‐limited, generating some concern for the adequacy of available data to address the question of interest. With conservation and management decisions often hinging on the status of species , it seems prudent to understand the capabilities of approaches we use given the data we have. Here, we apply two molecular species delimitation approaches, spedeSTEM and BPP, to the Castilleja ambigua (Orobanchaceae) species complex, a relatively young plant lineage in western North America. Upon finding incongruence in our delimitation, we employed a post hoc simulation study to examine the power of these approaches to delimit species. Given the data we collected, we find that spedeSTEM lacks the power to delimit while BPP is capable, thus allowing us to address incongruence before proceeding in delimitation. We suggest post hoc simulation studies like this compliment empirical delimitation and serve as a means of exploring conflict within a line of evidence and dealing with it appropriately.

Transformation in a changing climate: a research agenda - Ioan Fazey; Peter Moug; Simon Allen; Kate Beckmann; David Blackwood; Mike Bonaventura; Kathryn Burnett; Mike Danson; Ruth Falconer; Alexandre S. Gagnon; Rachel Harkness; Anthony Hodgson; et al. (Climate and Development, 2018)

Diet, the intestinal microbiota, and immune health in aging - Sarah J. Clements; Simon R. Carding (Critical Reviews in Food Science and Nutrition, 2018)

Plants eavesdrop on cues produced by snails and induce costly defenses that affect insect herbivores - John L. Orrock; Brian M. Connolly; Won-Gyu Choi; Peter W. Guiden; Sarah J. Swanson; Simon Gilroy (Oecologia, 2018)

Integrated ecological–economic fisheries models—Evaluation, review and challenges for implementation - J Rasmus Nielsen; Eric Thunberg; Daniel S Holland; Jorn O Schmidt; Elizabeth A Fulton; Francois Bastardie; Andre E Punt; Icarus Allen; Heleen Bartelings; Michel Bertignac; Eckhard Bethke; Sieme Bossier; et al. (Fish and Fisheries, 2018)
Marine ecosystems evolve under many interconnected and area‐specific pressures. To fulfil society's intensifying and diversifying needs while ensuring ecologically sustainable development, more effective marine spatial planning and broader‐scope management of marine resources is necessary. Integrated ecological–economic fisheries models ( IEEFM s) of marine systems are needed to evaluate impacts and sustainability of potential management actions and understand, and anticipate ecological, economic and social dynamics at a range of scales from local to national and regional. To make these models most effective, it is important to determine how model characteristics and methods of communicating results influence the model implementation, the nature of the advice that can be provided and the impact on decisions taken by managers. This article presents a global review and comparative evaluation of 35 IEEFM s applied to marine fisheries and marine ecosystem resources to identify the characteristics that determine their usefulness, effectiveness and implementation. The focus is on fully integrated models that allow for feedbacks between ecological and human processes although not all the models reviewed achieve that. Modellers must invest more time to make models user friendly and to participate in management fora where models and model results can be explained and discussed. Such involvement is beneficial to all parties, leading to improvement of mo‐dels and more effective implementation of advice, but demands substantial resources which must be built into the governance process. It takes time to develop effective processes for using IEEFM s requiring a long‐term commitment to integrating multidisciplinary modelling advice into management decision‐making.

A latent measure explains substantial variance in white matter microstructure across the newborn human brain - Emma J. Telford; Simon R. Cox; Sue Fletcher-Watson; Devasuda Anblagan; Sarah Sparrow; Rozalia Pataky; Alan Quigley; Scott I. Semple; Mark E. Bastin; James P. Boardman (Brain Structure and Function, 2017)

Drivers of nitrogen transfer in stream food webs across continents - Beth C. Norman; Matt R. Whiles; Sarah M. Collins; Alexander S. Flecker; Steve K. Hamilton; Sherri L. Johnson; Emma J. Rosi; Linda R. Ashkenas; William B. Bowden; Chelsea L. Crenshaw; Todd Crowl; Walter K. Dodds; et al. (Ecology, 2017)
Studies of trophic‐level material and energy transfers are central to ecology. The use of isotopic tracers has now made it possible to measure trophic transfer efficiencies of important nutrients and to better understand how these materials move through food webs. We analyzed data from thirteen 15 N‐ammonium tracer addition experiments to quantify N transfer from basal resources to animals in headwater streams with varying physical, chemical, and biological features. N transfer efficiencies from primary uptake compartments (PUCs; heterotrophic microorganisms and primary producers) to primary consumers was lower (mean 11.5%, range 100%). Total N transferred (as a rate) was greater in streams with open compared to closed canopies and overall N transfer efficiency generally followed a similar pattern, although was not statistically significant. We used principal component analysis to condense a suite of site characteristics into two environmental components. Total N uptake rates among trophic levels were best predicted by the component that was correlated with latitude, DIN:SRP, GPP:ER, and percent canopy cover. N transfer efficiency did not respond consistently to environmental variables. Our results suggest that canopy cover influences N movement through stream food webs because light availability and primary production facilitate N transfer to higher trophic levels.

Combined effects of agrochemicals and ecosystem services on crop yield across Europe - Vesna Gagic; David Kleijn; András Báldi; Gergely Boros; Helene Bracht Jørgensen; Zoltán Elek; Michael P. D. Garratt; G. Arjen de Groot; Katarina Hedlund; Anikó Kovács‐Hostyánszki; Lorenzo Marini; Emily Martin; et al. (Ecology Letters, 2017)
Simultaneously enhancing ecosystem services provided by biodiversity below and above ground is recommended to reduce dependence on chemical pesticides and mineral fertilisers in agriculture. However, consequences for crop yield have been poorly evaluated. Above ground, increased landscape complexity is assumed to enhance biological pest control, whereas below ground, soil organic carbon is a proxy for several yield‐supporting services. In a field experiment replicated in 114 fields across Europe, we found that fertilisation had the strongest positive effect on yield, but hindered simultaneous harnessing of below‐ and above‐ground ecosystem services. We furthermore show that enhancing natural enemies and pest control through increasing landscape complexity can prove disappointing in fields with low soil services or in intensively cropped regions. Thus, understanding ecological interdependences between land use, ecosystem services and yield is necessary to promote more environmentally friendly farming by identifying situations where ecosystem services are maximised and agrochemical inputs can be reduced.

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Lyophilization of an Adjuvanted Mycobacterium tuberculosis Vaccine in a Single-Chamber Pharmaceutical Cartridge - Lucien Barnes V; Dawn M. Fedor; Simon Williams; Quinton M. Dowling; Michelle C. Archer; Sylvain Cloutier; Sarah Parker; Thomas S. Vedvick; Christopher B. Fox; Ryan M. Kramer (AAPS PharmSciTech, 2017)

Semi‐quantitative reconstruction of early to late Holocene spring and summer sea ice conditions in the northern Barents Sea - Sarah M. P. Berben; Katrine Husum; Alba Navarro‐Rodriguez; Simon T. Belt; Steffen Aagaard‐Sørensen (Journal of Quaternary Science, 2017)
Semi‐quantitative estimates of early to late Holocene spring sea ice concentration (SpSIC) and occurrence of summer sea ice for the northern Barents Sea have been obtained by analysing the biomarkers IP 25 , brassicasterol and a tri‐unsaturated highly branched isoprenoid lipid in a Holocene marine sediment core. Sub‐surface water mass variations were derived from planktic foraminiferal assemblages and stable isotopes (δ 18 O, δ 13 C). The record indicates paleoceanographic changes over three intervals. During Period I (ca. 9500–5900 cal a BP), the study location experienced the lowest recorded SpSIC (ca. 25%) with short spring seasons and long productive summers, resulting partly from increased Atlantic Water inflow that caused a stronger ocean–atmosphere heat exchange. Throughout Period II (ca. 5900–2700 cal a BP), the winter sea ice margin migrated southwards and an overall cooling trend resulted in higher SpSIC (ca. 60%) and increased delivery of cold Arctic Water. During Period III (ca. 2700 cal a BP to present), SpSIC increased further (ca. 75%) and some sea ice remained during summer months. A sub‐surface warming probably indicates a decoupling of heat exchange between the ocean and the atmosphere. Longer springs and shorter summers were accompanied by the most southerly location of the winter sea ice margin.

Resting-state test–retest reliability of a priori defined canonical networks over different preprocessing steps - Deepthi P. Varikuti; Felix Hoffstaedter; Sarah Genon; Holger Schwender; Andrew T. Reid; Simon B. Eickhoff (Brain Structure and Function, 2017)

Don’t forget the porpoise: acoustic monitoring reveals fine scale temporal variation between bottlenose dolphin and harbour porpoise in Cardigan Bay SAC - Hanna K. Nuuttila; Winnie Courtene-Jones; Sarah Baulch; Malene Simon; Peter G. H. Evans (Marine Biology, 2017)

Pramipexole induced place preference after L-dopa therapy and nigral dopaminergic loss: linking behavior to transcriptional modifications - Simon Loiodice; Poppy Winlow; Sarah Dremier; Etienne Hanon; David Dardou; Omar Ouachikh; Aziz Hafidi; Andre Nogueira da Costa; Franck Durif (Psychopharmacology, 2017)

A Galaxy-based bioinformatics pipeline for optimised, streamlined microsatellite development from Illumina next-generation sequencing data - Sarah M. Griffiths; Graeme Fox; Peter J. Briggs; Ian J. Donaldson; Simon Hood; Pen Richardson; George W. Leaver; Nathan K. Truelove; Richard F. Preziosi (Conservation Genetics Resources, 2016)

Spatio‐temporal analysis of Nova virus, a divergent hantavirus circulating in the European mole in Belgium - Lies Laenen; Simon Dellicour; Valentijn Vergote; Inne Nauwelaers; Sarah De Coster; Ina Verbeeck; Bert Vanmechelen; Philippe Lemey; Piet Maes (Molecular Ecology, 2016)
Over the last decade, the recognized host range of hantaviruses has expanded considerably with the discovery of distinct hantaviruses in shrews, moles and bats. Unfortunately, in‐depth studies of these viruses have been limited. Here we describe a comprehensive analysis of the spatial distribution, genetic diversity and evolution of Nova virus, a hantavirus that has the European mole as its natural host. Our analysis demonstrated that Nova virus has a high prevalence and widespread distribution in Belgium. While Nova virus displayed relatively high nucleotide diversity in Belgium, amino acid changes were limited. The nucleocapsid protein was subjected to strong purifying selection, reflecting the strict evolutionary constraints placed upon Nova virus by its host. Spatio‐temporal analysis using Bayesian evolutionary inference techniques demonstrated that Nova virus had efficiently spread in the European mole population in Belgium, forming two distinct clades, representing east and west of Belgium. The influence of landscape barriers, in the form of the main waterways, on the dispersal velocity of Nova virus was assessed using an analytical framework for comparing Bayesian viral phylogenies with environmental landscape data. We demonstrated that waterways did not act as an environmental resistance factor slowing down Nova virus diffusion in the mole population. With this study, we provide information about the spatial diffusion of Nova virus and contribute sequence information that can be applied in further functional studies.

Polypharmacy and medication regimen complexity as factors associated with staff informant rated quality of life in residents of aged care facilities: a cross-sectional study - Samanta Lalic; Kris M. Jamsen; Barbara C. Wimmer; Edwin C.K. Tan; Sarah N. Hilmer; Leonie Robson; Tina Emery; J. Simon Bell (European Journal of Clinical Pharmacology, 2016)

Rethinking Social Barriers to Effective Adaptive Management - Simon West; Lisen Schultz; Sarah Bekessy (Environmental Management, 2016)

The Role of Holocene Relative Sea-Level Change in Preserving Records of Subduction Zone Earthquakes - Tina Dura; Simon E. Engelhart; Matteo Vacchi; Benjamin P. Horton; Robert E. Kopp; W. Richard Peltier; Sarah Bradley (Current Climate Change Reports, 2016)

Thidiazuron induces high-frequency indirect shoot organogenesis of Bienertia sinuspersici: a single-cell C4 species - Jennifer Anne Northmore; Dustin Sigurdson; Sarah Schoor; Amer Rustum; Simon D. X. Chuong (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

The OPAL bugs count survey: exploring the effects of urbanisation and habitat characteristics using citizen science - Adam J. Bates; Poppy Lakeman Fraser; Lucy Robinson; John C. Tweddle; Jon P. Sadler; Sarah E. West; Simon Norman; Martin Batson; Linda Davies (Urban Ecosystems, 2015)

Infrastructure for collaborative science and societal applications in the Columbia River estuary - António M. Baptista; Charles Seaton; Michael P. Wilkin; Sarah F. Riseman; Joseph A. Needoba; David Maier; Paul J. Turner; Tuomas Kärnä; Jesse E. Lopez; Lydie Herfort; V. M. Megler; Craig McNeil; et al. (Frontiers of Earth Science, 2015)
To meet societal needs, modern estuarine science needs to be interdisciplinary and collaborative, combine discovery with hypotheses testing, and be responsive to issues facing both regional and global stakeholders. Such an approach is best conducted with the benefit of data-rich environments, where information from sensors and models is openly accessible within convenient timeframes. Here, we introduce the operational infrastructure of one such data-rich environment, a collaboratory created to support (a) interdisciplinary research in the Columbia River estuary by the multi-institutional team of investigators of the Science and Technology Center for Coastal Margin Observation & Prediction and (b) the integration of scientific knowledge into regional decision making. Core components of the operational infrastructure are an observation network, a modeling system and a cyber-infrastructure, each of which is described. The observation network is anchored on an extensive array of long-term stations, many of them interdisciplinary, and is complemented by on-demand deployment of temporary stations and mobile platforms, often in coordinated field campaigns. The modeling system is based on finiteelement unstructured-grid codes and includes operational and process-oriented simulations of circulation, sediments and ecosystem processes. The flow of information is managed through a dedicated cyber-infrastructure, conversant with regional and national observing systems.

Forest restoration following surface mining disturbance: challenges and solutions - S. Ellen Macdonald; Simon M. Landhäusser; Jeff Skousen; Jennifer Franklin; Jan Frouz; Sarah Hall; Douglass F. Jacobs; Sylvie Quideau (New Forests, 2015)

A predictive model of the cat cortical connectome based on cytoarchitecture and distance - Sarah F. Beul; Simon Grant; Claus C. Hilgetag (Brain Structure and Function, 2015)

Marine protist diversity in E uropean coastal waters and sediments as revealed by high‐throughput sequencing - Ramon Massana; Angélique Gobet; Stéphane Audic; David Bass; Lucie Bittner; Christophe Boutte; Aurélie Chambouvet; Richard Christen; Jean‐Michel Claverie; Johan Decelle; John R. Dolan; Micah Dunthorn; et al. (Environmental Microbiology, 2015)
Summary Although protists are critical components of marine ecosystems, they are still poorly characterized. Here we analysed the taxonomic diversity of planktonic and benthic protist communities collected in six distant E uropean coastal sites. Environmental deoxyribonucleic acid ( DNA ) and ribonucleic acid ( RNA ) from three size fractions (pico‐, nano‐ and micro/mesoplankton), as well as from dissolved DNA and surface sediments were used as templates for tag pyrosequencing of the V4 region of the 18S ribosomal DNA. Beta‐diversity analyses split the protist community structure into three main clusters: picoplankton‐nanoplankton‐dissolved DNA , micro/mesoplankton and sediments. Within each cluster, protist communities from the same site and time clustered together, while communities from the same site but different seasons were unrelated. Both DNA and RNA ‐based surveys provided similar relative abundances for most class‐level taxonomic groups. Yet, particular groups were overrepresented in one of the two templates, such as marine alveolates ( MALV )‐ I and MALV‐II that were much more abundant in DNA surveys. Overall, the groups displaying the highest relative contribution were Dinophyceae, Diatomea, Ciliophora and Acantharia. Also, well represented were Mamiellophyceae, Cryptomonadales, marine alveolates and marine stramenopiles in the picoplankton, and Monadofilosa and basal F ungi in sediments. Our extensive and systematic sequencing of geographically separated sites provides the most comprehensive molecular description of coastal marine protist diversity to date.

Insights into the Genetic Foundations of Human Communication - Sarah A. Graham; Pelagia Deriziotis; Simon E. Fisher (Neuropsychology Review, 2015)

Risk factors for endometrial cancer in black and white women: a pooled analysis from the epidemiology of endometrial cancer consortium (E2C2) - Michele L. Cote; Tala Alhajj; Julie J. Ruterbusch; Leslie Bernstein; Louise A. Brinton; William J. Blot; Chu Chen; Margery Gass; Sarah Gaussoin; Brian Henderson; Eunjung Lee; Pamela L. Horn-Ross; et al. (Cancer Causes & Control, 2015)

Shifted neuronal balance during stimulus–response integration in schizophrenia: an fMRI study - Edna C. Cieslik; Veronika I. Müller; Tanja S. Kellermann; Christian Grefkes; Sarah Halfter; Simon B. Eickhoff (Brain Structure and Function, 2015)

Response to commentary by W oinarski (Critical‐weight‐range marsupials in northern A ustralia are declining: a commentary on Fisher et al . (2014) ‘The current decline of tropical marsupials in A ustralia: is history repeating?’) - Diana O. Fisher; Chris N. Johnson; Michael J. Lawes; Susanne A. Fritz; Hamish McCallum; Simon P. Blomberg; Jeremy VanDerWal; Brett Abbott; Anke Frank; Sarah Legge; Mike Letnic; Colette R. Thomas; et al. (Global Ecology and Biogeography, 2015)
The recent commentary by Woinarski (2014, Global Ecology and Biogeography , doi: 10.1111/geb.12165) disagreed with our conclusions on the correlates of decline in the marsupials of tropical A ustralia (Fisher et al., 2014, Global Ecology and Biogeography , 23 , 181–190). We compared traits of species that were associated with range decline in southern and northern A ustralia. We found that habitat structure, climate and body size were correlated with range decline. In the north, declines of marsupials were most severe in savanna with moderate rainfall. In the south, the ranges of species in open habitat with very low rainfall have declined most. Also, the association between range decline and body mass differed between north and south: this is the main concern of Woinarski, who further disagreed with our choice of the T ropic of C apricorn as a boundary between north and south, our omission of rodents, how to treat timing of extinctions, and our inference that cats are major drivers of decline. W e address these concerns in this response.

Climate change and Southern Ocean ecosystems I: how changes in physical habitats directly affect marine biota - Andrew J. Constable; Jessica Melbourne‐Thomas; Stuart P. Corney; Kevin R. Arrigo; Christophe Barbraud; David K. A. Barnes; Nathaniel L. Bindoff; Philip W. Boyd; Angelika Brandt; Daniel P. Costa; Andrew T. Davidson; Hugh W. Ducklow; et al. (Global Change Biology, 2014)
Antarctic and Southern Ocean ( ASO ) marine ecosystems have been changing for at least the last 30 years, including in response to increasing ocean temperatures and changes in the extent and seasonality of sea ice; the magnitude and direction of these changes differ between regions around Antarctica that could see populations of the same species changing differently in different regions. This article reviews current and expected changes in ASO physical habitats in response to climate change. It then reviews how these changes may impact the autecology of marine biota of this polar region: microbes, zooplankton, salps, Antarctic krill, fish, cephalopods, marine mammals, seabirds, and benthos. The general prognosis for ASO marine habitats is for an overall warming and freshening, strengthening of westerly winds, with a potential pole‐ward movement of those winds and the frontal systems, and an increase in ocean eddy activity. Many habitat parameters will have regionally specific changes, particularly relating to sea ice characteristics and seasonal dynamics. Lower trophic levels are expected to move south as the ocean conditions in which they are currently found move pole‐ward. For Antarctic krill and finfish, the latitudinal breadth of their range will depend on their tolerance of warming oceans and changes to productivity. Ocean acidification is a concern not only for calcifying organisms but also for crustaceans such as Antarctic krill; it is also likely to be the most important change in benthic habitats over the coming century. For marine mammals and birds, the expected changes primarily relate to their flexibility in moving to alternative locations for food and the energetic cost of longer or more complex foraging trips for those that are bound to breeding colonies. Few species are sufficiently well studied to make comprehensive species‐specific vulnerability assessments possible. Priorities for future work are discussed.

Septicaemia models using Streptococcus pneumoniae and Listeria monocytogenes: understanding the role of complement properdin - Aline Dupont; Fatima Mohamed; Nur’Ain Salehen; Sarah Glenn; Lorenza Francescut; Rozita Adib; Simon Byrne; Hannah Brewin; Irina Elliott; Luke Richards; Petya Dimitrova; Wilhelm Schwaeble; et al. (Medical Microbiology and Immunology, 2014)

Aborigine‐managed forest, savanna and grassland: biome switching in montane eastern Australia - Don W. Butler; Roderick J. Fensham; Brett P. Murphy; Simon G. Haberle; Sarah J. Bury; David M. J. S. Bowman (Journal of Biogeography, 2014)
Aim To assess hypotheses about the role of anthropogenic fire in the maintenance and origin of a fine‐scale vegetation mosaic of rain forest, eucalypt savanna and grassland. Location Bunya Mountains, subtropical eastern Australia. Methods A time series of vegetation maps was compiled from historical and recent aerial photography and field surveys. Geospatial models were constructed of environmental domains for rain forest, savanna and grassland, and for areas of biome change. Grassland soils were analysed for carbon isotope ratios (δ 13 C), and radiocarbon ( 14 C) dates were acquired for bulk samples from a range of depths. Results Analysis revealed weak associations between topography and the distribution of rain forest, savanna and grassland, and their patterns of recent change. Grassland occupied an environmental domain intermediate between rain forest and savanna and was more than four times as likely to occur within a matrix of rain forest rather than savanna. There was a large proportional reduction in the area of both grassland (−35%) and savanna (−19%) between 1961 and 2006 because of the expansion of rain forest. However, the greater initial extent of savanna meant that the areal loss of savanna was an order of magnitude greater than for grassland (1433 vs. 146 ha). There was no evidence of abrupt changes in δ 13 C in grassland soil profiles, indicating stability of the vegetation over the last 2000 years. Main conclusions There is no simple gradient in ‘tree suitability’ from rain forest, through savanna, to treeless grassland on the Bunya Mountains. A general absence of fire since the 19th century has greatly reduced the extent of grassy savanna and grassland formations, to the advantage of rain forest. These results support the hypothesis that the vegetation mosaic on the Bunya Mountains is a cultural artefact and testament to millennia of skilful and persistent burning. We could not conclusively reject the hypothesis that the grasslands are Pleistocene relicts that have declined throughout the Holocene; nonetheless, an explanation more consistent with the evidence overall is that the grasslands must have had periods of expansion during the Holocene, probably as a consequence of severe fires that have destroyed patches of rain forest.

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Experimenting with ecosystem interaction networks in search of threshold potentials in real‐world marine ecosystems - Simon F. Thrush; Judi E. Hewitt; Samantha Parkes; Andrew M. Lohrer; Conrad Pilditch; Sarah A. Woodin; David S. Wethey; Mariachiara Chiantore; Valentina Asnaghi; Silvia De Juan; Casper Kraan; Ivan Rodil; et al. (Ecology, 2014)
Thresholds profoundly affect our understanding and management of ecosystem dynamics, but we have yet to develop practical techniques to assess the risk that thresholds will be crossed. Combining ecological knowledge of critical system interdependencies with a large‐scale experiment, we tested for breaks in the ecosystem interaction network to identify threshold potential in real‐world ecosystem dynamics. Our experiment with the bivalves Macomona liliana and Austrovenus stutchburyi on marine sandflats in New Zealand demonstrated that reductions in incident sunlight changed the interaction network between sediment biogeochemical fluxes, productivity, and macrofauna. By demonstrating loss of positive feedbacks and changes in the architecture of the network, we provide mechanistic evidence that stressors lead to break points in dynamics, which theory predicts predispose a system to a critical transition.

A Framework for Quantitative Assessment of Impacts Related to Energy and Mineral Resource Development - Seth S. Haines; Jay E. Diffendorfer; Laurie Balistrieri; Byron Berger; Troy Cook; Don DeAngelis; Holly Doremus; Donald L. Gautier; Tanya Gallegos; Margot Gerritsen; Elisabeth Graffy; Sarah Hawkins; et al. (Natural Resources Research, 2014)

The current decline of tropical marsupials in A ustralia: is history repeating? - Diana O. Fisher; Chris N. Johnson; Michael J. Lawes; Susanne A. Fritz; Hamish McCallum; Simon P. Blomberg; Jeremy VanDerWal; Brett Abbott; Anke Frank; Sarah Legge; Mike Letnic; Colette R. Thomas; et al. (Global Ecology and Biogeography, 2014)
Aim A third of all modern (after 1500) mammal extinctions (24/77) are Australian species. These extinctions have been restricted to southern A ustralia, predominantly in species of ‘critical weight range’ (35–5500 g) in drier climate zones. Introduced red foxes ( V ulpes vulpes ) that prey on species in this range are often blamed. A new wave of declines is now affecting a globally significant proportion of marsupial species (19 species) in the fox‐free northern tropics. We aim to test plausible causes of recent declines in range and determine if mechanisms differ between current tropical declines and past declines, which were in southern (non‐tropical) regions. Location A ustralian continent Methods We used multiple regression and random forest models to analyse traits that were associated with declines in species range, and compare variables associated with past extinctions in the southern zones with current tropical (northern) declines. Results The same two key variables, body mass and habitat structure, were associated with proportion‐of‐decline in range throughout the continent, but the form of relationships differs with latitude. In the south, medium‐sized species in open habitats of lower rainfall were most likely to decline. In the tropics, small species that occupy open vegetation with moderate rainfall (savanna) are now experiencing the most severe declines. Throughout the continent, large‐bodied species and those in structurally complex habitats (rainforest) are secure. Main conclusions Our results indicate that there is no mid‐sized ‘critical weight range’ in the north. Because foxes are absent from the tropics, we suggest that northern Australian marsupial declines are associated with predation by feral cats ( F elis catus ) exacerbated by reduced ground level vegetation in non‐rainforest habitats. To test this, we recommend experiments to remove cats from some locations where tropical mammals are threatened. Our results show that comparative analysis can help to diagnose potential causes of multi‐species decline.

Inertia in an ombrotrophic bog ecosystem in response to 9 years' realistic perturbation by wet deposition of nitrogen, separated by form - Lucy J. Sheppard; Ian D. Leith; Toshie Mizunuma; Sarah Leeson; Sanna Kivimaki; J. Neil Cape; Netty van Dijk; David Leaver; Mark A. Sutton; David Fowler; Leon J.L. Van den Berg; Alan Crossley; et al. (Global Change Biology, 2014)
Wet deposition of nitrogen (N) occurs in oxidized (nitrate) and reduced (ammonium) forms. Whether one form drives vegetation change more than the other is widely debated, as field evidence has been lacking. We are manipulating N form in wet deposition to an ombrotrophic bog, Whim (Scottish Borders), and here report nine years of results. Ammonium and nitrate were provided in rainwater spray as NH 4 Cl or NaNO 3 at 8, 24 or 56 kg N ha −1 yr −1 , plus a rainwater only control, via an automated system coupled to site meteorology. Detrimental N effects were observed in sensitive nonvascular plant species, with higher cumulative N loads leading to more damage at lower annual doses. Cover responses to N addition, both in relation to form and dose, were species specific and mostly dependent on N dose. Some species were generally indifferent to N form and dose, while others were dose sensitive. Calluna vulgaris showed a preference for higher N doses as ammonium N and Hypnum jutlandicum for nitrate N. However, after 9 years, the magnitude of change from wet deposited N on overall species cover is small, indicating only a slow decline in key species. Nitrogen treatment effects on soil N availability were likewise small and rarely correlated with species cover. Ammonium caused most N accumulation and damage to sensitive species at lower N loads, but toxic effects also occurred with nitrate. However, because different species respond differently to N form, setting of ecosystem level critical loads by N form is challenging. We recommend implementing the lowest value of the critical load range where communities include sensitive nonvascular plants and where ammonium dominates wet deposition chemistry. In the context of parallel assessment at the same site, N treatments for wet deposition showed overall much smaller effects than corresponding inputs of dry deposition as ammonia.

Prediction of human core body temperature using non-invasive measurement methods - Reto Niedermann; Eva Wyss; Simon Annaheim; Agnes Psikuta; Sarah Davey; René Michel Rossi (International Journal of Biometeorology, 2014)

A systematic review of brain frontal lobe parcellation techniques in magnetic resonance imaging - Simon R. Cox; Karen J. Ferguson; Natalie A. Royle; Susan D. Shenkin; Sarah E. MacPherson; Alasdair M. J. MacLullich; Ian J. Deary; Joanna M. Wardlaw (Brain Structure and Function, 2014)

Morph-dependent resource acquisition and fitness in a polymorphic bird - James Brazill-Boast; Simon C. Griffith; Sarah R. Pryke (Evolutionary Ecology, 2013)

Minor contribution of leaf litter to N nutrition of beech (Fagus sylvatica) seedlings in a mountainous beech forest of Southern Germany - Chanjuan Guo; Judy Simon; Rainer Gasche; Pascale Sarah Naumann; Carolin Bimüller; Rodica Pena; Andrea Polle; Ingrid Kögel-Knabner; Bernd Zeller; Heinz Rennenberg; Michael Dannenmann (Plant and Soil, 2013)

A global quantitative synthesis of local and landscape effects on wild bee pollinators in agroecosystems - Christina M. Kennedy; Eric Lonsdorf; Maile C. Neel; Neal M. Williams; Taylor H. Ricketts; Rachael Winfree; Riccardo Bommarco; Claire Brittain; Alana L. Burley; Daniel Cariveau; Luísa G. Carvalheiro; Natacha P. Chacoff; et al. (Ecology Letters, 2013)
Bees provide essential pollination services that are potentially affected both by local farm management and the surrounding landscape. To better understand these different factors, we modelled the relative effects of landscape composition (nesting and floral resources within foraging distances), landscape configuration (patch shape, interpatch connectivity and habitat aggregation) and farm management (organic vs. conventional and local‐scale field diversity), and their interactions, on wild bee abundance and richness for 39 crop systems globally. Bee abundance and richness were higher in diversified and organic fields and in landscapes comprising more high‐quality habitats; bee richness on conventional fields with low diversity benefited most from high‐quality surrounding land cover. Landscape configuration effects were weak. Bee responses varied slightly by biome. Our synthesis reveals that pollinator persistence will depend on both the maintenance of high‐quality habitats around farms and on local management practices that may offset impacts of intensive monoculture agriculture.

Asynchronous food‐web pathways could buffer the response of Serengeti predators to El Niño Southern Oscillation - A. R. E. Sinclair; Kristine L. Metzger; John M. Fryxell; Craig Packer; Andrea E. Byrom; Meggan E. Craft; Katie Hampson; Tiziana Lembo; Sarah M. Durant; Guy J. Forrester; John Bukombe; John Mchetto; et al. (Ecology, 2013)
Understanding how entire ecosystems maintain stability in the face of climatic and human disturbance is one of the most fundamental challenges in ecology. Theory suggests that a crucial factor determining the degree of ecosystem stability is simply the degree of synchrony with which different species in ecological food webs respond to environmental stochasticity. Ecosystems in which all food‐web pathways are affected similarly by external disturbance should amplify variability in top carnivore abundance over time due to population interactions, whereas ecosystems in which a large fraction of pathways are nonresponsive or even inversely responsive to external disturbance will have more constant levels of abundance at upper trophic levels. To test the mechanism underlying this hypothesis, we used over half a century of demographic data for multiple species in the Serengeti (Tanzania) ecosystem to measure the degree of synchrony to variation imposed by an external environmental driver, the El Niño Southern Oscillation (ENSO). ENSO effects were mediated largely via changes in dry‐season vs. wet‐season rainfall and consequent changes in vegetation availability, propagating via bottom‐up effects to higher levels of the Serengeti food web to influence herbivores, predators and parasites. Some species in the Serengeti food web responded to the influence of ENSO in opposite ways, whereas other species were insensitive to variation in ENSO. Although far from conclusive, our results suggest that a diffuse mixture of herbivore responses could help buffer top carnivores, such as Serengeti lions, from variability in climate. Future global climate changes that favor some pathways over others, however, could alter the effectiveness of such processes in the future.

Lead and Arsenic Uptake by Leafy Vegetables Grown on Contaminated Soils: Effects of Mineral and Organic Amendments - Murray B. McBride; Tobi Simon; Geoffrey Tam; Sarah Wharton (Water, Air, & Soil Pollution, 2013)

A genome-wide association study of breast cancer in women of African ancestry - Fang Chen; Gary K. Chen; Daniel O. Stram; Robert C. Millikan; Christine B. Ambrosone; Esther M. John; Leslie Bernstein; Wei Zheng; Julie R. Palmer; Jennifer J. Hu; Tim R. Rebbeck; Regina G. Ziegler; et al. (Human Genetics, 2013)

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

Cryptic microtextures and geological histories of K-rich alkali feldspars revealed by charge contrast imaging - Stephanie Flude; Martin R. Lee; Sarah C. Sherlock; Simon P. Kelley (Contributions to Mineralogy and Petrology, 2012)

Polymorphic variants in tenascin-C (TNC) are associated with atherosclerosis and coronary artery disease - Mollie A. Minear; David R. Crosslin; Beth S. Sutton; Jessica J. Connelly; Sarah C. Nelson; Shera Gadson-Watson; Tianyuan Wang; David Seo; Jeffrey M. Vance; Michael H. Sketch; Carol Haynes; Pascal J. Goldschmidt-Clermont; et al. (Human Genetics, 2011)

Production of food-associated calls in wild male chimpanzees is dependent on the composition of the audience - Katie E. Slocombe; Tanja Kaller; Laurel Turman; Simon W. Townsend; Sarah Papworth; Paul Squibbs; Klaus Zuberbühler (Behavioral Ecology and Sociobiology, 2010)

Comparative life cycle assessment of margarine and butter consumed in the UK, Germany and France - Katarina Nilsson; Anna Flysjö; Jennifer Davis; Sarah Sim; Nicole Unger; Simon Bell (The International Journal of Life Cycle Assessment, 2010)

Dissecting regulatory pathways of G1/S control in Arabidopsis: common and distinct targets of CYCD3;1, E2Fa and E2Fc - Sarah M. de Jager; Simon Scofield; Rachael P. Huntley; Alastair S. Robinson; Bart G. W. den Boer; James A. H. Murray (Plant Molecular Biology, 2009)

Crawl-out behaviour in response to predation cues in an aquatic gastropod: insights from artificial selection - Sarah Dalesman; Simon D. Rundle; Peter A. Cotton (Evolutionary Ecology, 2009)

Genetic effects in the leukotriene biosynthesis pathway and association with atherosclerosis - David R. Crosslin; Svati H. Shah; Sarah C. Nelson; Carol S. Haynes; Jessica J. Connelly; Shera Gadson; Pascal J. Goldschmidt-Clermont; Jeffery M. Vance; Jason Rose; Chris B. Granger; David Seo; Simon G. Gregory; et al. (Human Genetics, 2009)

Variation analysis and gene annotation of eight MHC haplotypes: The MHC Haplotype Project - Roger Horton; Richard Gibson; Penny Coggill; Marcos Miretti; Richard J. Allcock; Jeff Almeida; Simon Forbes; James G. R. Gilbert; Karen Halls; Jennifer L. Harrow; Elizabeth Hart; Kevin Howe; et al. (Immunogenetics, 2008)

Pollination and other ecosystem services produced by mobile organisms: a conceptual framework for the effects of land‐use change - Claire Kremen; Neal M. Williams; Marcelo A. Aizen; Barbara Gemmill‐Herren; Gretchen LeBuhn; Robert Minckley; Laurence Packer; Simon G. Potts; T'ai Roulston; Ingolf Steffan‐Dewenter; Diego P. Vázquez; Rachael Winfree; et al. (Ecology Letters, 2007)
Many ecosystem services are delivered by organisms that depend on habitats that are segregated spatially or temporally from the location where services are provided. Management of mobile organisms contributing to ecosystem services requires consideration not only of the local scale where services are delivered, but also the distribution of resources at the landscape scale, and the foraging ranges and dispersal movements of the mobile agents. We develop a conceptual model for exploring how one such mobile‐agent‐based ecosystem service (MABES), pollination, is affected by land‐use change, and then generalize the model to other MABES. The model includes interactions and feedbacks among policies affecting land use, market forces and the biology of the organisms involved. Animal‐mediated pollination contributes to the production of goods of value to humans such as crops; it also bolsters reproduction of wild plants on which other services or service‐providing organisms depend. About one‐third of crop production depends on animal pollinators, while 60–90% of plant species require an animal pollinator. The sensitivity of mobile organisms to ecological factors that operate across spatial scales makes the services provided by a given community of mobile agents highly contextual. Services vary, depending on the spatial and temporal distribution of resources surrounding the site, and on biotic interactions occurring locally, such as competition among pollinators for resources, and among plants for pollinators. The value of the resulting goods or services may feed back via market‐based forces to influence land‐use policies, which in turn influence land management practices that alter local habitat conditions and landscape structure. Developing conceptual models for MABES aids in identifying knowledge gaps, determining research priorities, and targeting interventions that can be applied in an adaptive management context.

Place-based urban ecology: A century of park planning in Seattle - Sarah Dooling; Gregory Simon; Ken Yocom (Urban Ecosystems, 2006)

Feo – Transport of Ferrous Iron into Bacteria - Michaël L. Cartron; Sarah Maddocks; Paul Gillingham; C. Jeremy Craven; Simon C. Andrews (BioMetals, 2006)

Climate variability and campylobacter infection: an international study - R. Sari Kovats; Sally J. Edwards; Dominique Charron; John Cowden; Rennie M. D’Souza; Kristie L. Ebi; Charmaine Gauci; Peter Gerner-Smidt; Shakoor Hajat; Simon Hales; Gloria Hernández Pezzi; Bohumir Kriz; et al. (International Journal of Biometeorology, 2005)

Identification and characterization of a novel mouse prion gene allele - Sarah E. Lloyd; Simon R. Thompson; Jonathan A. Beck; Jacqueline M. Linehan; Jonathan D. F. Wadsworth; Sebastian Brandner; John Collinge; Elizabeth M. C. Fisher (Mammalian Genome, 2004)

Sequence variation in the CHAT locus shows no association with late-onset Alzheimer's disease - Denise Harold; Timothy Peirce; Valentina Moskvina; Simon Lovestone; John Powell; Catherine Foy; Nicola Archer; Sarah Walter; Amanda Edmonson; Stephen McIlroy; David Craig; Peter A. Passmore; et al. (Human Genetics, 2003)

Increases in cytosolic Ca 2+ are not required for abscisic acid-inhibition of inward K + currents in guard cells of Vicia faba L. - Lisa A. Romano; Tobias Jacob; Simon Gilroy; Sarah M. Assmann (Planta, 2000)

An integrated genetic linkage map of the laboratory rat - Donna M. Brown *, Tara C. Matise; George Koike; Jason S. Simon; Eric S. Winer; Sarah Zangen; Michael G. McLaughlin; Masahide Shiozawa; O. Scott Atkinson; James R. Hudson, Jr.; Aravinda Chakravarti; Eric S. Lander **, Howard (Mammalian Genome, 1998)